Cryo-EM structure of a functional monomeric Photosystem I from Thermosynechococcus elongatus reveals red chlorophyll cluster - Çoruh, Mehmet Orkun; Frank, Anna; Tanaka, Hideaki; Kawamoto, Akihiro; El-Mohsnawy, Eithar; Kato, Takayuki; Namba, Keiichi; Gerle, Christoph; Nowaczyk, Marc M.; Kurisu, Genji (Communications Biology)
A high-resolution structure of trimeric cyanobacterial Photosystem I (PSI) from Thermosynechococcus elongatus was reported as the first atomic model of PSI almost 20 years ago. However, the monomeric PSI structure has not yet been reported despite long-standing interest in its structure and extensive spectroscopic characterization of the loss of red chlorophylls upon monomerization. Here, we describe the structure of monomeric PSI from Thermosynechococcus elongatus BP-1. Comparison with the trimer structure gave detailed insights into monomerization-induced changes in both the central trimerization domain and the peripheral regions of the complex. Monomerization-induced loss of red chlorophylls is assigned to a cluster of chlorophylls adjacent to PsaX. Based on our findings, we propose a role of PsaX in the stabilization of red chlorophylls and that lipids of the surrounding membrane present a major source of thermal energy for uphill excitation energy transfer from red chlorophylls to P700.
Keywords: general agricultural and biological Sciences; general biochemistry; genetics and molecular biology; medicine (miscellaneous)

Histone H1 prevents non-CG methylation-mediated small RNA biogenesis in Arabidopsis heterochromatin - Choi, Jaemyung; Lyons, David B; Zilberman, Daniel (eLife)
Flowering plants utilize small RNA molecules to guide DNA methyltransferases to genomic sequences. This RNA-directed DNA methylation (RdDM) pathway preferentially targets euchromatic transposable elements. However, RdDM is thought to be recruited by methylation of histone H3 at lysine 9 (H3K9me), a hallmark of heterochromatin. How RdDM is targeted to euchromatin despite an affinity for H3K9me is unclear. Here we show that loss of histone H1 enhances heterochromatic RdDM, preferentially at nucleosome linker DNA. Surprisingly, this does not require SHH1, the RdDM component that binds H3K9me. Furthermore, H3K9me is dispensable for RdDM, as is CG DNA methylation. Instead, we find that non-CG methylation is specifically associated with small RNA biogenesis, and without H1 small RNA production quantitatively expands to non-CG methylated loci. Our results demonstrate that H1 enforces the separation of euchromatic and heterochromatic DNA methylation pathways by excluding the small RNA-generating branch of RdDM from non-CG methylated heterochromatin.
Keywords: genetics and molecular biology

Loss of Hem1 disrupts macrophage function and impacts migration, phagocytosis, and integrin-mediated adhesion - Stahnke, Stephanie; Döring, Hermann; Kusch, Charly; de Gorter, David J.J.; Dütting, Sebastian; Guledani, Aleks; Pleines, Irina; Schnoor, Michael; Sixt, Michael K; Geffers, Robert; Rohde, Manfred; Müsken, Mathias; et al. (Current Biology)
Hematopoietic-specific protein 1 (Hem1) is an essential subunit of the WAVE regulatory complex (WRC) in immune cells. WRC is crucial for Arp2/3 complex activation and the protrusion of branched actin filament networks. Moreover, Hem1 loss of function in immune cells causes autoimmune diseases in humans. Here, we show that genetic removal of Hem1 in macrophages diminishes frequency and efficacy of phagocytosis as well as phagocytic cup formation in addition to defects in lamellipodial protrusion and migration. Moreover, Hem1-null macrophages displayed strong defects in cell adhesion despite unaltered podosome formation and concomitant extracellular matrix degradation. Specifically, dynamics of both adhesion and de-adhesion as well as concomitant phosphorylation of paxillin and focal adhesion kinase (FAK) were significantly compromised. Accordingly, disruption of WRC function in non-hematopoietic cells coincided with both defects in adhesion turnover and altered FAK and paxillin phosphorylation. Consistently, platelets exhibited reduced adhesion and diminished integrin αIIbβ3 activation upon WRC removal. Interestingly, adhesion phenotypes, but not lamellipodia formation, were partially rescued by small molecule activation of FAK. A full rescue of the phenotype, including lamellipodia formation, required not only the presence of WRCs but also their binding to and activation by Rac. Collectively, our results uncover that WRC impacts on integrin-dependent processes in a FAK-dependent manner, controlling formation and dismantling of adhesions, relevant for properly grabbing onto extracellular surfaces and particles during cell edge expansion, like in migration or phagocytosis.
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology

Computational toolbox for ultrastructural quantitative analysis of filament networks in cryo-ET data - Dimchev, Georgi A; Amiri, Behnam; Fäßler, Florian; Falcke, Martin; Schur, Florian KM (Journal of Structural Biology)
A precise quantitative description of the ultrastructural characteristics underlying biological mechanisms is often key to their understanding. This is particularly true for dynamic extra- and intracellular filamentous assemblies, playing a role in cell motility, cell integrity, cytokinesis, tissue formation and maintenance. For example, genetic manipulation or modulation of actin regulatory proteins frequently manifests in changes of the morphology, dynamics, and ultrastructural architecture of actin filament-rich cell peripheral structures, such as lamellipodia or filopodia. However, the observed ultrastructural effects often remain subtle and require sufficiently large datasets for appropriate quantitative analysis. The acquisition of such large datasets has been enabled by recent advances in high-throughput cryo-electron tomography (cryo-ET) methods. This also necessitates the development of complementary approaches to maximize the extraction of relevant biological information. We have developed a computational toolbox for the semi-automatic quantification of segmented and vectorized filamentous networks from pre-processed cryo-electron tomograms, facilitating the analysis and cross-comparison of multiple experimental conditions. GUI-based components simplify the processing of data and allow users to obtain a large number of ultrastructural parameters describing filamentous assemblies. We demonstrate the feasibility of this workflow by analyzing cryo-ET data of untreated and chemically perturbed branched actin filament networks and that of parallel actin filament arrays. In principle, the computational toolbox presented here is applicable for data analysis comprising any type of filaments in regular (i.e. parallel) or random arrangement. We show that it can ease the identification of key differences between experimental groups and facilitate the in-depth analysis of ultrastructural data in a time-efficient manner.
Keywords: Structural Biology

Minimal biophysical model of combined antibiotic action - Kavcic, Bor; Tkačik, Gašper; Bollenbach, Tobias (PLOS Computational Biology)
Phenomenological relations such as Ohm’s or Fourier’s law have a venerable history in physics but are still scarce in biology. This situation restrains predictive theory. Here, we build on bacterial “growth laws,” which capture physiological feedback between translation and cell growth, to construct a minimal biophysical model for the combined action of ribosome-targeting antibiotics. Our model predicts drug interactions like antagonism or synergy solely from responses to individual drugs. We provide analytical results for limiting cases, which agree well with numerical results. We systematically refine the model by including direct physical interactions of different antibiotics on the ribosome. In a limiting case, our model provides a mechanistic underpinning for recent predictions of higher-order interactions that were derived using entropy maximization. We further refine the model to include the effects of antibiotics that mimic starvation and the presence of resistance genes. We describe the impact of a starvation-mimicking antibiotic on drug interactions analytically and verify it experimentally. Our extended model suggests a change in the type of drug interaction that depends on the strength of resistance, which challenges established rescaling paradigms. We experimentally show that the presence of unregulated resistance genes can lead to altered drug interaction, which agrees with the prediction of the model. While minimal, the model is readily adaptable and opens the door to predicting interactions of second and higher-order in a broad range of biological systems.
Keywords: Modelling and Simulation; Genetics; Molecular Biology; Antibiotics; Drug interactions

Local genetic context shapes the function of a gene regulatory network - Nagy-Staron, Anna A; Tomasek, Kathrin; Caruso Carter, Caroline; Sonnleitner, Elisabeth; Kavcic, Bor; Paixão, Tiago; Guet, Calin C (eLife)
Gene expression levels are influenced by multiple coexisting molecular mechanisms. Some of these interactions such as those of transcription factors and promoters have been studied extensively. However, predicting phenotypes of gene regulatory networks (GRNs) remains a major challenge. Here, we use a well-defined synthetic GRN to study in Escherichia coli how network phenotypes depend on local genetic context, i.e. the genetic neighborhood of a transcription factor and its relative position. We show that one GRN with fixed topology can display not only quantitatively but also qualitatively different phenotypes, depending solely on the local genetic context of its components. Transcriptional read-through is the main molecular mechanism that places one transcriptional unit (TU) within two separate regulons without the need for complex regulatory sequences. We propose that relative order of individual TUs, with its potential for combinatorial complexity, plays an important role in shaping phenotypes of GRNs.
Keywords: Genetics and Molecular Biology

Reading the chromatinized genome - Michael, Alicia; Thomä, Nicolas H. (Cell)
Eukaryotic DNA-binding proteins operate in the context of chromatin, where nucleosomes are the elementary building blocks. Nucleosomal DNA is wrapped around a histone core, thereby rendering a large fraction of the DNA surface inaccessible to DNA-binding proteins. Nevertheless, first responders in DNA repair and sequence-specific transcription factors bind DNA target sites obstructed by chromatin. While early studies examined protein binding to histone-free DNA, it is only now beginning to emerge how DNA sequences are interrogated on nucleosomes. These readout strategies range from the release of nucleosomal DNA from histones, to rotational/translation register shifts of the DNA motif, and nucleosome-specific DNA binding modes that differ from those observed on naked DNA. Since DNA motif engagement on nucleosomes strongly depends on position and orientation, we argue that motif location and nucleosome positioning co-determine protein access to DNA in transcription and DNA repair.
Keywords: General Biochemistry; Genetics and Molecular Biology

The actin-disassembly protein glia maturation factor γ enhances actin remodeling and B cell antigen receptor signaling at the immune synapse - Deretic, Nikola; Bolger-Munro, Madison; Choi, Kate; Abraham, Libin; Gold, Michael R. (Frontiers in Cell and Developmental Biology)
Signaling by the B cell antigen receptor (BCR) initiates actin remodeling. The assembly of branched actin networks that are nucleated by the Arp2/3 complex exert outward force on the plasma membrane, allowing B cells to form membrane protrusions that can scan the surface of antigen-presenting cells (APCs). The resulting Arp2/3 complex-dependent actin retrograde flow promotes the centripetal movement and progressive coalescence of BCR microclusters, which amplifies BCR signaling. Glia maturation factor γ (GMFγ) is an actin disassembly-protein that releases Arp2/3 complex-nucleated actin filaments from actin networks. By doing so, GMFγ could either oppose the actions of the Arp2/3 complex or support Arp2/3 complex-nucleated actin polymerization by contributing to the recycling of actin monomers and Arp2/3 complexes. We now show that reducing the levels of GMFγ in human B cell lines via transfection with a specific siRNA impairs the ability of B cells to spread on antigen-coated surfaces, decreases the velocity of actin retrograde flow, diminishes the coalescence of BCR microclusters into a central cluster at the B cell-APC contact site, and decreases APC-induced BCR signaling. These effects of depleting GMFγ are similar to what occurs when the Arp2/3 complex is inhibited. This suggests that GMFγ cooperates with the Arp2/3 complex to support BCR-induced actin remodeling and amplify BCR signaling at the immune synapse.
Keywords: Cell Biology; Developmental Biology

Dynamics of hunchback translation in real-time and at single-mRNA resolution in the Drosophila embryo - Vinter, Daisy J.; Hoppe, Caroline; Minchington, Thomas; Sutcliffe, Catherine; Ashe, Hilary L. (Development)
The Hunchback (Hb) transcription factor is crucial for anterior-posterior patterning of the Drosophila embryo. The maternal hb mRNA acts as a paradigm for translational regulation due to its repression in the posterior of the embryo. However, little is known about the translatability of zygotically transcribed hb mRNAs. Here, we adapt the SunTag system, developed for imaging translation at single-mRNA resolution in tissue culture cells, to the Drosophila embryo to study the translation dynamics of zygotic hb mRNAs. Using single-molecule imaging in fixed and live embryos, we provide evidence for translational repression of zygotic SunTag-hb mRNAs. Whereas the proportion of SunTag-hb mRNAs translated is initially uniform, translation declines from the anterior over time until it becomes restricted to a posterior band in the expression domain. We discuss how regulated hb mRNA translation may help establish the sharp Hb expression boundary, which is a model for precision and noise during developmental patterning. Overall, our data show how use of the SunTag method on fixed and live embryos is a powerful combination for elucidating spatiotemporal regulation of mRNA translation in Drosophila.
Keywords: Developmental Biology; Molecular Biology

The Pleiades are a cluster of fungal effectors that inhibit host defenses - Navarrete, Fernando; Grujic, Nenad; Stirnberg, Alexandra; Saado, Indira; Aleksza, David; Gallei, Michelle C; Adi, Hazem; Alcântara, André; Khan, Mamoona; Bindics, Janos; Trujillo, Marco; Djamei, Armin (PLOS Pathogens)
Biotrophic plant pathogens secrete effector proteins to manipulate the host physiology. Effectors suppress defenses and induce an environment favorable to disease development. Sequence-based prediction of effector function is impeded by their rapid evolution rate. In the maize pathogen Ustilago maydis , effector-coding genes frequently organize in clusters. Here we describe the functional characterization of the pleiades , a cluster of ten effector genes, by analyzing the micro- and macroscopic phenotype of the cluster deletion and expressing these proteins in planta . Deletion of the pleiades leads to strongly impaired virulence and accumulation of reactive oxygen species (ROS) in infected tissue. Eight of the Pleiades suppress the production of ROS upon perception of pathogen associated molecular patterns (PAMPs). Although functionally redundant, the Pleiades target different host components. The paralogs Taygeta1 and Merope1 suppress ROS production in either the cytoplasm or nucleus, respectively. Merope1 targets and promotes the auto-ubiquitination activity of RFI2, a conserved family of E3 ligases that regulates the production of PAMP-triggered ROS burst in plants.
Keywords: Virology; Genetics; Molecular Biology; Immunology; Microbiology; Parasitology

Incomplete removal of extracellular glutamate controls synaptic transmission and integration at a cerebellar synapse - Balmer, Timothy S; Borges Merjane, Carolina; Trussell, Laurence O (eLife)
Synapses of glutamatergic mossy fibers (MFs) onto cerebellar unipolar brush cells (UBCs) generate slow excitatory (ON) or inhibitory (OFF) postsynaptic responses dependent on the complement of glutamate receptors expressed on the UBC’s large dendritic brush. Using mouse brain slice recording and computational modeling of synaptic transmission, we found that substantial glutamate is maintained in the UBC synaptic cleft, sufficient to modify spontaneous firing in OFF UBCs and tonically desensitize AMPARs of ON UBCs. The source of this ambient glutamate was spontaneous, spike-independent exocytosis from the MF terminal, and its level was dependent on activity of glutamate transporters EAAT1–2. Increasing levels of ambient glutamate shifted the polarity of evoked synaptic responses in ON UBCs and altered the phase of responses to in vivo-like synaptic activity. Unlike classical fast synapses, receptors at the UBC synapse are virtually always exposed to a significant level of glutamate, which varies in a graded manner during transmission.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

The CATP-8/P5A-type ATPase functions in multiple pathways during neuronal patterning - Tang, Leo T. H.; Trivedi, Meera; Freund, Jenna; Salazar, Christopher J.; Rahman, Maisha; Ramirez, Nelson; Lee, Garrett; Wang, Yu; Grant, Barth D.; Bülow, Hannes E. (PLOS Genetics)
The assembly of neuronal circuits involves the migrations of neurons from their place of birth to their final location in the nervous system, as well as the coordinated growth and patterning of axons and dendrites. In screens for genes required for patterning of the nervous system, we identified the catp-8/P5A-ATPase as an important regulator of neural patterning. P5A-ATPases are part of the P-type ATPases, a family of proteins known to serve a conserved function as transporters of ions, lipids and polyamines in unicellular eukaryotes, plants, and humans. While the function of many P-type ATPases is relatively well understood, the function of P5A-ATPases in metazoans remained elusive. We show here, that the Caenorhabditis elegans ortholog catp-8/P5A-ATPase is required for defined aspects of nervous system development. Specifically, the catp-8/P5A-ATPase serves functions in shaping the elaborately sculpted dendritic trees of somatosensory PVD neurons. Moreover, catp-8/P5A-ATPase is required for axonal guidance and repulsion at the midline, as well as embryonic and postembryonic neuronal migrations. Interestingly, not all axons at the midline require catp-8/P5A-ATPase , although the axons run in the same fascicles and navigate the same space. Similarly, not all neuronal migrations require catp-8/P5A-ATPase . A CATP-8/P5A-ATPase reporter is localized to the ER in most, if not all, tissues and catp-8/P5A-ATPase can function both cell-autonomously and non-autonomously to regulate neuronal development. Genetic analyses establish that catp-8/P5A-ATPase can function in multiple pathways, including the Menorin pathway, previously shown to control dendritic patterning in PVD, and Wnt signaling, which functions to control neuronal migrations. Lastly, we show that catp-8/P5A-ATPase is required for localizing select transmembrane proteins necessary for dendrite morphogenesis. Collectively, our studies suggest that catp-8/P5A-ATPase serves diverse, yet specific, roles in different genetic pathways and may be involved in the regulation or localization of transmembrane and secreted proteins to specific subcellular compartments.
Keywords: Cancer Research; Genetics (clinical); Genetics; Molecular Biology; Ecology; Evolution; Behavior and Systematics

Reassembling gastrulation - Schauer, Alexandra; Heisenberg, Carl-Philipp J (Developmental Biology)
During development, a single cell is transformed into a highly complex organism through progressive cell division, specification and rearrangement. An important prerequisite for the emergence of patterns within the developing organism is to establish asymmetries at various scales, ranging from individual cells to the entire embryo, eventually giving rise to the different body structures. This becomes especially apparent during gastrulation, when the earliest major lineage restriction events lead to the formation of the different germ layers. Traditionally, the unfolding of the developmental program from symmetry breaking to germ layer formation has been studied by dissecting the contributions of different signaling pathways and cellular rearrangements in the in vivo context of intact embryos. Recent efforts, using the intrinsic capacity of embryonic stem cells to self-assemble and generate embryo-like structures de novo, have opened new avenues for understanding the many ways by which an embryo can be built and the influence of extrinsic factors therein. Here, we discuss and compare divergent and conserved strategies leading to germ layer formation in embryos as compared to in vitro systems, their upstream molecular cascades and the role of extrinsic factors in this process.
Keywords: Developmental Biology; Cell Biology; Molecular Biology

Cul3 regulates cytoskeleton protein homeostasis and cell migration during a critical window of brain development - Morandell, Jasmin; Schwarz, Lena A; Basilico, Bernadette; Tasciyan, Saren; Dimchev, Georgi A; Nicolas, Armel; Sommer, Christoph M; Kreuzinger, Caroline; Dotter, Christoph; Knaus, Lisa; Dobler, Zoe; Cacci, Emanuele; et al. (Nature Communications)
De novo loss of function mutations in the ubiquitin ligase-encoding gene Cullin3 lead to autism spectrum disorder (ASD). In mouse, constitutive haploinsufficiency leads to motor coordination deficits as well as ASD-relevant social and cognitive impairments. However, induction of Cul3 haploinsufficiency later in life does not lead to ASD-relevant behaviors, pointing to an important role of Cul3 during a critical developmental window. Here we show that Cul3 is essential to regulate neuronal migration and, therefore, constitutive Cul3 heterozygous mutant mice display cortical lamination abnormalities. At the molecular level, we found that Cul3 controls neuronal migration by tightly regulating the amount of Plastin3 (Pls3), a previously unrecognized player of neural migration. Furthermore, we found that Pls3 cell-autonomously regulates cell migration by regulating actin cytoskeleton organization, and its levels are inversely proportional to neural migration speed. Finally, we provide evidence that cellular phenotypes associated with autism-linked gene haploinsufficiency can be rescued by transcriptional activation of the intact allele in vitro, offering a proof of concept for a potential therapeutic approach for ASDs.
Keywords: General Biochemistry; Genetics and Molecular Biology

An ESCRT-III polymerization sequence drives membrane deformation and fission - Pfitzner, Anna-Katharina; Mercier, Vincent; Jiang, Xiuyun; Moser von Filseck, Joachim; Baum, Buzz; Šarić, Anđela; Roux, Aurélien (Cell)
The endosomal sorting complex required for transport-III (ESCRT-III) catalyzes membrane fission from within membrane necks, a process that is essential for many cellular functions, from cell division to lysosome degradation and autophagy. How it breaks membranes, though, remains unknown. Here, we characterize a sequential polymerization of ESCRT-III subunits that, driven by a recruitment cascade and by continuous subunit-turnover powered by the ATPase Vps4, induces membrane deformation and fission. During this process, the exchange of Vps24 for Did2 induces a tilt in the polymer-membrane interface, which triggers transition from flat spiral polymers to helical filament to drive the formation of membrane protrusions, and ends with the formation of a highly constricted Did2-Ist1 co-polymer that we show is competent to promote fission when bound on the inside of membrane necks. Overall, our results suggest a mechanism of stepwise changes in ESCRT-III filament structure and mechanical properties via exchange of the filament subunits to catalyze ESCRT-III activity.
Keywords: general biochemistry; genetics and molecular biology

Transcriptional and functional changes of the human microvasculature during physiological aging and Alzheimer disease - Bersini, Simone; Arrojo e Drigo, Rafael; Huang, Ling; Shokhirev, Maxim N.; HETZER, Martin W (Advanced Biosystems)
Aging of the circulatory system correlates with the pathogenesis of a large spectrum of diseases. However, it is largely unknown which factors drive the age-dependent or pathological decline of the vasculature and how vascular defects relate to tissue aging. The goal of the study is to design a multianalytical approach to identify how the cellular microenvironment (i.e., fibroblasts) and serum from healthy donors of different ages or Alzheimer disease (AD) patients can modulate the functionality of organ-specific vascular endothelial cells (VECs). Long-living human microvascular networks embedding VECs and fibroblasts from skin biopsies are generated. RNA-seq, secretome analyses, and microfluidic assays demonstrate that fibroblasts from young donors restore the functionality of aged endothelial cells, an effect also achieved by serum from young donors. New biomarkers of vascular aging are validated in human biopsies and it is shown that young serum induces angiopoietin-like-4, which can restore compromised vascular barriers. This strategy is then employed to characterize transcriptional/functional changes induced on the blood–brain barrier by AD serum, demonstrating the importance of PTP4A3 in the regulation of permeability. Features of vascular degeneration during aging and AD are recapitulated, and a tool to identify novel biomarkers that can be exploited to develop future therapeutics modulating vascular function is established.
Keywords: General Biochemistry; Genetics and Molecular Biology; Biomedical Engineering; Biomaterials

Direct reprogramming of human smooth muscle and vascular endothelial cells reveals defects associated with aging and Hutchinson-Gilford progeria syndrome - Bersini, Simone; Schulte, Roberta; Huang, Ling; Tsai, Hannah; HETZER, Martin W (eLife)
Vascular dysfunctions are a common feature of multiple age-related diseases. However, modeling healthy and pathological aging of the human vasculature represents an unresolved experimental challenge. Here, we generated induced vascular endothelial cells (iVECs) and smooth muscle cells (iSMCs) by direct reprogramming of healthy human fibroblasts from donors of different ages and Hutchinson-Gilford Progeria Syndrome (HGPS) patients. iVECs induced from old donors revealed upregulation of GSTM1 and PALD1, genes linked to oxidative stress, inflammation and endothelial junction stability, as vascular aging markers. A functional assay performed on PALD1 KD VECs demonstrated a recovery in vascular permeability. We found that iSMCs from HGPS donors overexpressed bone morphogenetic protein (BMP)−4, which plays a key role in both vascular calcification and endothelial barrier damage observed in HGPS. Strikingly, BMP4 concentrations are higher in serum from HGPS vs. age-matched mice. Furthermore, targeting BMP4 with blocking antibody recovered the functionality of the vascular barrier in vitro, hence representing a potential future therapeutic strategy to limit cardiovascular dysfunction in HGPS. These results show that iVECs and iSMCs retain disease-related signatures, allowing modeling of vascular aging and HGPS in vitro.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

Dynamic regulation of histone modifications and long-range chromosomal interactions during postmitotic transcriptional reactivation - Kang, Hyeseon; Shokhirev, Maxim N.; Xu, Zhichao; Chandran, Sahaana; Dixon, Jesse R.; HETZER, Martin W (Genes & Development)
During mitosis, transcription of genomic DNA is dramatically reduced, before it is reactivated during nuclear reformation in anaphase/telophase. Many aspects of the underlying principles that mediate transcriptional memory and reactivation in the daughter cells remain unclear. Here, we used ChIP-seq on synchronized cells at different stages after mitosis to generate genome-wide maps of histone modifications. Combined with EU-RNA-seq and Hi-C analyses, we found that during prometaphase, promoters, enhancers, and insulators retain H3K4me3 and H3K4me1, while losing H3K27ac. Enhancers globally retaining mitotic H3K4me1 or locally retaining mitotic H3K27ac are associated with cell type-specific genes and their transcription factors for rapid transcriptional activation. As cells exit mitosis, promoters regain H3K27ac, which correlates with transcriptional reactivation. Insulators also gain H3K27ac and CCCTC-binding factor (CTCF) in anaphase/telophase. This increase of H3K27ac in anaphase/telophase is required for posttranscriptional activation and may play a role in the establishment of topologically associating domains (TADs). Together, our results suggest that the genome is reorganized in a sequential order, in which histone methylations occur first in prometaphase, histone acetylation, and CTCF in anaphase/telophase, transcription in cytokinesis, and long-range chromatin interactions in early G1. We thus provide insights into the histone modification landscape that allows faithful reestablishment of the transcriptional program and TADs during cell division.
Keywords: Developmental Biology; Genetics

Nup93 regulates breast tumor growth by modulating cell proliferation and actin cytoskeleton remodeling - Bersini, Simone; Lytle, Nikki K; Schulte, Roberta; Huang, Ling; Wahl, Geoffrey M; HETZER, Martin W (Life Science Alliance)
Nucleoporin 93 (Nup93) expression inversely correlates with the survival of triple-negative breast cancer patients. However, our knowledge of Nup93 function in breast cancer besides its role as structural component of the nuclear pore complex is not understood. Combination of functional assays and genetic analyses suggested that chromatin interaction of Nup93 partially modulates the expression of genes associated with actin cytoskeleton remodeling and epithelial to mesenchymal transition, resulting in impaired invasion of triple-negative, claudin-low breast cancer cells. Nup93 depletion induced stress fiber formation associated with reduced cell migration/proliferation and impaired expression of mesenchymal-like genes. Silencing LIMCH1, a gene responsible for actin cytoskeleton remodeling and up-regulated upon Nup93 depletion, partially restored the invasive phenotype of cancer cells. Loss of Nup93 led to significant defects in tumor establishment/propagation in vivo, whereas patient samples revealed that high Nup93 and low LIMCH1 expression correlate with late tumor stage. Our approach identified Nup93 as contributor of triple-negative, claudin-low breast cancer cell invasion and paves the way to study the role of nuclear envelope proteins during breast cancer tumorigenesis.
Keywords: Health; Toxicology and Mutagenesis; Plant Science; Biochemistry; Genetics and Molecular Biology (miscellaneous); Ecology

The mitochondrial carrier pathway transports non-canonical substrates with an odd number of transmembrane segments - Rampelt, Heike; Sucec, Iva; Bersch, Beate; Horten, Patrick; Perschil, Inge; Martinou, Jean-Claude; van der Laan, Martin; Wiedemann, Nils; Schanda, Paul; Pfanner, Nikolaus (BMC Biology)
Background: The mitochondrial pyruvate carrier (MPC) plays a central role in energy metabolism by transporting pyruvate across the inner mitochondrial membrane. Its heterodimeric composition and homology to SWEET and semiSWEET transporters set the MPC apart from the canonical mitochondrial carrier family (named MCF or SLC25). The import of the canonical carriers is mediated by the carrier translocase of the inner membrane (TIM22) pathway and is dependent on their structure, which features an even number of transmembrane segments and both termini in the intermembrane space. The import pathway of MPC proteins has not been elucidated. The odd number of transmembrane segments and positioning of the N-terminus in the matrix argues against an import via the TIM22 carrier pathway but favors an import via the flexible presequence pathway. Results: Here, we systematically analyzed the import pathways of Mpc2 and Mpc3 and report that, contrary to an expected import via the flexible presequence pathway, yeast MPC proteins with an odd number of transmembrane segments and matrix-exposed N-terminus are imported by the carrier pathway, using the receptor Tom70, small TIM chaperones, and the TIM22 complex. The TIM9·10 complex chaperones MPC proteins through the mitochondrial intermembrane space using conserved hydrophobic motifs that are also required for the interaction with canonical carrier proteins. Conclusions: The carrier pathway can import paired and non-paired transmembrane helices and translocate N-termini to either side of the mitochondrial inner membrane, revealing an unexpected versatility of the mitochondrial import pathway for non-cleavable inner membrane proteins.
Keywords: Biotechnology; Plant Science; General Biochemistry; Genetics and Molecular Biology; Developmental Biology; Cell Biology; Physiology; Ecology; Evolution; Behavior and Systematics; Structural Biology; General Agricultural and Biological Sciences

AXR1 affects DNA methylation independently of its role in regulating meiotic crossover localization - Christophorou, Nicolas; She, Wenjing; Long, Jincheng; Hurel, Aurélie; Beaubiat, Sébastien; Idir, Yassir; Tagliaro-Jahns, Marina; Chambon, Aurélie; Solier, Victor; Vezon, Daniel; Grelon, Mathilde; Feng, Xiaoqi; et al. (PLOS Genetics)
Meiotic crossovers (COs) are important for reshuffling genetic information between homologous chromosomes and they are essential for their correct segregation. COs are unevenly distributed along chromosomes and the underlying mechanisms controlling CO localization are not well understood. We previously showed that meiotic COs are mis-localized in the absence of AXR1, an enzyme involved in the neddylation/rubylation protein modification pathway in Arabidopsis thaliana. Here, we report that in axr1-/-, male meiocytes show a strong defect in chromosome pairing whereas the formation of the telomere bouquet is not affected. COs are also redistributed towards subtelomeric chromosomal ends where they frequently form clusters, in contrast to large central regions depleted in recombination. The CO suppressed regions correlate with DNA hypermethylation of transposable elements (TEs) in the CHH context in axr1-/- meiocytes. Through examining somatic methylomes, we found axr1-/- affects DNA methylation in a plant, causing hypermethylation in all sequence contexts (CG, CHG and CHH) in TEs. Impairment of the main pathways involved in DNA methylation is epistatic over axr1-/- for DNA methylation in somatic cells but does not restore regular chromosome segregation during meiosis. Collectively, our findings reveal that the neddylation pathway not only regulates hormonal perception and CO distribution but is also, directly or indirectly, a major limiting pathway of TE DNA methylation in somatic cells.
Keywords: Cancer Research; Genetics (clinical); Genetics; Molecular Biology; Ecology; Evolution; Behavior and Systematics

Converting microwave and telecom photons with a silicon photonic nanomechanical interface - Arnold, Georg M; Wulf, Matthias; Barzanjeh, Shabir; Redchenko, Elena; Rueda Sanchez, Alfredo R; Hease, William J; Hassani, Farid; Fink, Johannes M (Nature Communications)
Practical quantum networks require low-loss and noise-resilient optical interconnects as well as non-Gaussian resources for entanglement distillation and distributed quantum computation. The latter could be provided by superconducting circuits but existing solutions to interface the microwave and optical domains lack either scalability or efficiency, and in most cases the conversion noise is not known. In this work we utilize the unique opportunities of silicon photonics, cavity optomechanics and superconducting circuits to demonstrate a fully integrated, coherent transducer interfacing the microwave X and the telecom S bands with a total (internal) bidirectional transduction efficiency of 1.2% (135%) at millikelvin temperatures. The coupling relies solely on the radiation pressure interaction mediated by the femtometer-scale motion of two silicon nanobeams reaching a V π as low as 16 μV for sub-nanowatt pump powers. Without the associated optomechanical gain, we achieve a total (internal) pure conversion efficiency of up to 0.019% (1.6%), relevant for future noise-free operation on this qubit-compatible platform.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Physics and Astronomy; General Chemistry

Oncogenic state and cell identity combinatorially dictate the susceptibility of cells within glioma development hierarchy to IGF1R targeting - Tian, Anhao; Kang, Bo; Li, Baizhou; Qiu, Biying; Jiang, Wenhong; Shao, Fangjie; Gao, Qingqing; Liu, Rui; Cai, Chengwei; Jing, Rui; Wang, Wei; Chen, Pengxiang; et al. (Advanced Science)
Glioblastoma is the most malignant cancer in the brain and currently incurable. It is urgent to identify effective targets for this lethal disease. Inhibition of such targets should suppress the growth of cancer cells and, ideally also precancerous cells for early prevention, but minimally affect their normal counterparts. Using genetic mouse models with neural stem cells (NSCs) or oligodendrocyte precursor cells (OPCs) as the cells‐of‐origin/mutation, it is shown that the susceptibility of cells within the development hierarchy of glioma to the knockout of insulin‐like growth factor I receptor (IGF1R) is determined not only by their oncogenic states, but also by their cell identities/states. Knockout of IGF1R selectively disrupts the growth of mutant and transformed, but not normal OPCs, or NSCs. The desirable outcome of IGF1R knockout on cell growth requires the mutant cells to commit to the OPC identity regardless of its development hierarchical status. At the molecular level, oncogenic mutations reprogram the cellular network of OPCs and force them to depend more on IGF1R for their growth. A new‐generation brain‐penetrable, orally available IGF1R inhibitor harnessing tumor OPCs in the brain is also developed. The findings reveal the cellular window of IGF1R targeting and establish IGF1R as an effective target for the prevention and treatment of glioblastoma.
Keywords: General Engineering; General Physics and Astronomy; General Materials Science; Medicine (miscellaneous); General Chemical Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous)

Persistent and reversible solid iodine electrodeposition in nanoporous carbons - Prehal, Christian; Fitzek, Harald; Kothleitner, Gerald; Presser, Volker; Gollas, Bernhard; Freunberger, Stefan Alexander; Abbas, Qamar (Nature Communications)
Aqueous iodine based electrochemical energy storage is considered a potential candidate to improve sustainability and performance of current battery and supercapacitor technology. It harnesses the redox activity of iodide, iodine, and polyiodide species in the confined geometry of nanoporous carbon electrodes. However, current descriptions of the electrochemical reaction mechanism to interconvert these species are elusive. Here we show that electrochemical oxidation of iodide in nanoporous carbons forms persistent solid iodine deposits. Confinement slows down dissolution into triiodide and pentaiodide, responsible for otherwise significant self-discharge via shuttling. The main tools for these insights are in situ Raman spectroscopy and in situ small and wide-angle X-ray scattering (in situ SAXS/WAXS). In situ Raman confirms the reversible formation of triiodide and pentaiodide. In situ SAXS/WAXS indicates remarkable amounts of solid iodine deposited in the carbon nanopores. Combined with stochastic modeling, in situ SAXS allows quantifying the solid iodine volume fraction and visualizing the iodine structure on 3D lattice models at the sub-nanometer scale. Based on the derived mechanism, we demonstrate strategies for improved iodine pore filling capacity and prevention of self-discharge, applicable to hybrid supercapacitors and batteries.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Physics and Astronomy; General Chemistry

Cysteine oxidation and disulfide formation in the ribosomal exit tunnel - Schulte, Linda; Mao, Jiafei; Reitz, Julian; Sreeramulu, Sridhar; Kudlinzki, Denis; Hodirnau, Victor-Valentin; Meier-Credo, Jakob; Saxena, Krishna; Buhr, Florian; Langer, Julian D.; Blackledge, Martin; Frangakis, Achilleas S.; et al. (Nature Communications)
Understanding the conformational sampling of translation-arrested ribosome nascent chain complexes is key to understand co-translational folding. Up to now, coupling of cysteine oxidation, disulfide bond formation and structure formation in nascent chains has remained elusive. Here, we investigate the eye-lens protein γB-crystallin in the ribosomal exit tunnel. Using mass spectrometry, theoretical simulations, dynamic nuclear polarization-enhanced solid-state nuclear magnetic resonance and cryo-electron microscopy, we show that thiol groups of cysteine residues undergo S-glutathionylation and S-nitrosylation and form non-native disulfide bonds. Thus, covalent modification chemistry occurs already prior to nascent chain release as the ribosome exit tunnel provides sufficient space even for disulfide bond formation which can guide protein folding.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Physics and Astronomy; General Chemistry

The Moran process on 2-chromatic graphs - Kaveh, Kamran; McAvoy, Alex; Chatterjee, Krishnendu; Nowak, Martin A. (PLOS Computational Biology)
Resources are rarely distributed uniformly within a population. Heterogeneity in the concentration of a drug, the quality of breeding sites, or wealth can all affect evolutionary dynamics. In this study, we represent a collection of properties affecting the fitness at a given location using a color. A green node is rich in resources while a red node is poorer. More colors can represent a broader spectrum of resource qualities. For a population evolving according to the birth-death Moran model, the first question we address is which structures, identified by graph connectivity and graph coloring, are evolutionarily equivalent. We prove that all properly two-colored, undirected, regular graphs are evolutionarily equivalent (where “properly colored” means that no two neighbors have the same color). We then compare the effects of background heterogeneity on properly two-colored graphs to those with alternative schemes in which the colors are permuted. Finally, we discuss dynamic coloring as a model for spatiotemporal resource fluctuations, and we illustrate that random dynamic colorings often diminish the effects of background heterogeneity relative to a proper two-coloring.
Keywords: Ecology; Modelling and Simulation; Computational Theory and Mathematics; Genetics; Ecology; Evolution; Behavior and Systematics; Molecular Biology; Cellular and Molecular Neuroscience

Cryo-electron tomography structure of Arp2/3 complex in cells reveals new insights into the branch junction - Fäßler, Florian; Dimchev, Georgi A; Hodirnau, Victor-Valentin; Wan, William; Schur, Florian KM (Nature Communications)
The actin-related protein (Arp)2/3 complex nucleates branched actin filament networks pivotal for cell migration, endocytosis and pathogen infection. Its activation is tightly regulated and involves complex structural rearrangements and actin filament binding, which are yet to be understood. Here, we report a 9.0 Å resolution structure of the actin filament Arp2/3 complex branch junction in cells using cryo-electron tomography and subtomogram averaging. This allows us to generate an accurate model of the active Arp2/3 complex in the branch junction and its interaction with actin filaments. Notably, our model reveals a previously undescribed set of interactions of the Arp2/3 complex with the mother filament, significantly different to the previous branch junction model. Our structure also indicates a central role for the ArpC3 subunit in stabilizing the active conformation.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Physics and Astronomy; General Chemistry

SCIM: Universal single-cell matching with unpaired feature sets - Stark, Stefan G; Ficek, Joanna; Locatello, Francesco; Bonilla, Ximena; Chevrier, Stéphane; Singer, Franziska; Aebersold, Rudolf; Al-Quaddoomi, Faisal S; Albinus, Jonas; Alborelli, Ilaria; Andani, Sonali; Attinger, Per-Olof; et al. (Bioinformatics)
Motivation: Recent technological advances have led to an increase in the production and availability of single-cell data. The ability to integrate a set of multi-technology measurements would allow the identification of biologically or clinically meaningful observations through the unification of the perspectives afforded by each technology. In most cases, however, profiling technologies consume the used cells and thus pairwise correspondences between datasets are lost. Due to the sheer size single-cell datasets can acquire, scalable algorithms that are able to universally match single-cell measurements carried out in one cell to its corresponding sibling in another technology are needed. Results: We propose Single-Cell data Integration via Matching (SCIM), a scalable approach to recover such correspondences in two or more technologies. SCIM assumes that cells share a common (low-dimensional) underlying structure and that the underlying cell distribution is approximately constant across technologies. It constructs a technology-invariant latent space using an autoencoder framework with an adversarial objective. Multi-modal datasets are integrated by pairing cells across technologies using a bipartite matching scheme that operates on the low-dimensional latent representations. We evaluate SCIM on a simulated cellular branching process and show that the cell-to-cell matches derived by SCIM reflect the same pseudotime on the simulated dataset. Moreover, we apply our method to two real-world scenarios, a melanoma tumor sample and a human bone marrow sample, where we pair cells from a scRNA dataset to their sibling cells in a CyTOF dataset achieving 90% and 78% cell-matching accuracy for each one of the samples, respectively.
Keywords: Computational Mathematics; Computational Theory and Mathematics; Computer Science Applications; Molecular Biology; Biochemistry; Statistics and Probability

Sequences of gene regulatory network permutations for the article "Local genetic context shapes the function of a gene regulatory network" - Nagy-Staron, Anna A
Gene expression levels are influenced by multiple coexisting molecular mechanisms. Some of these interactions, such as those of transcription factors and promoters have been studied extensively. However, predicting phenotypes of gene regulatory networks remains a major challenge. Here, we use a well-defined synthetic gene regulatory network to study how network phenotypes depend on local genetic context, i.e. the genetic neighborhood of a transcription factor and its relative position. We show that one gene regulatory network with fixed topology can display not only quantitatively but also qualitatively different phenotypes, depending solely on the local genetic context of its components. Our results demonstrate that changes in local genetic context can place a single transcriptional unit within two separate regulons without the need for complex regulatory sequences. We propose that relative order of individual transcriptional units, with its potential for combinatorial complexity, plays an important role in shaping phenotypes of gene regulatory networks.
Keywords: Gene regulatory networks; Gene expression; Escherichia coli; Synthetic Biology

TOLs function as ubiquitin receptors in the early steps of the ESCRT pathway in higher plants - Moulinier-Anzola, Jeanette; Schwihla, Maximilian; De-Araújo, Lucinda; Artner, Christina; Jörg, Lisa; Konstantinova, Nataliia; Luschnig, Christian; Korbei, Barbara (Molecular Plant)
Protein abundance and localization at the plasma membrane (PM) shapes plant development and mediates adaptation to changing environmental conditions. It is regulated by ubiquitination, a post-translational modification crucial for the proper sorting of endocytosed PM proteins to the vacuole for subsequent degradation. To understand the significance and the variety of roles played by this reversible modification, the function of ubiquitin receptors, which translate the ubiquitin signature into a cellular response, needs to be elucidated. In this study, we show that TOL (TOM1-like) proteins function in plants as multivalent ubiquitin receptors, governing ubiquitinated cargo delivery to the vacuole via the conserved Endosomal Sorting Complex Required for Transport (ESCRT) pathway. TOL2 and TOL6 interact with components of the ESCRT machinery and bind to K63-linked ubiquitin via two tandemly arranged conserved ubiquitin-binding domains. Mutation of these domains results not only in a loss of ubiquitin binding but also altered localization, abolishing TOL6 ubiquitin receptor activity. Function and localization of TOL6 is itself regulated by ubiquitination, whereby TOL6 ubiquitination potentially modulates degradation of PM-localized cargoes, assisting in the fine-tuning of the delicate interplay between protein recycling and downregulation. Taken together, our findings demonstrate the function and regulation of a ubiquitin receptor that mediates vacuolar degradation of PM proteins in higher plants.
Keywords: Plant Science; Molecular Biology

Molecular recognition at septin interfaces: The switches hold the key - Rosa, Higor Vinícius Dias; Leonardo, Diego Antonio; Brognara, Gabriel; Brandão-Neto, José; D'Muniz Pereira, Humberto; Araújo, Ana Paula Ulian; Garratt, Richard Charles (Journal of Molecular Biology)
The assembly of a septin filament requires that homologous monomers must distinguish between one another in establishing appropriate interfaces with their neighbors. To understand this phenomenon at the molecular level, we present the first four crystal structures of heterodimeric septin complexes. We describe in detail the two distinct types of G-interface present within the octameric particles, which must polymerize to form filaments. These are formed between SEPT2 and SEPT6 and between SEPT7 and SEPT3, and their description permits an understanding of the structural basis for the selectivity necessary for correct filament assembly. By replacing SEPT6 by SEPT8 or SEPT11, it is possible to rationalize Kinoshita's postulate, which predicts the exchangeability of septins from within a subgroup. Switches I and II, which in classical small GTPases provide a mechanism for nucleotide-dependent conformational change, have been repurposed in septins to play a fundamental role in molecular recognition. Specifically, it is switch I which holds the key to discriminating between the two different G-interfaces. Moreover, residues which are characteristic for a given subgroup play subtle, but pivotal, roles in guaranteeing that the correct interfaces are formed.
Keywords: Molecular Biology; Structural Biology

Dynamics at the serine loop underlie differential affinity of cryptochromes for CLOCK:BMAL1 to control circadian timing - Fribourgh, Jennifer L; Srivastava, Ashutosh; Sandate, Colby R; Michael, Alicia Kathleen; Hsu, Peter L; Rakers, Christin; Nguyen, Leslee T; Torgrimson, Megan R; Parico, Gian Carlo G; Tripathi, Sarvind; Zheng, Ning; Lander, Gabriel C; et al. (eLife)
Mammalian circadian rhythms are generated by a transcription-based feedback loop in which CLOCK:BMAL1 drives transcription of its repressors (PER1/2, CRY1/2), which ultimately interact with CLOCK:BMAL1 to close the feedback loop with ~24 hr periodicity. Here we pinpoint a key difference between CRY1 and CRY2 that underlies their differential strengths as transcriptional repressors. Both cryptochromes bind the BMAL1 transactivation domain similarly to sequester it from coactivators and repress CLOCK:BMAL1 activity. However, we find that CRY1 is recruited with much higher affinity to the PAS domain core of CLOCK:BMAL1, allowing it to serve as a stronger repressor that lengthens circadian period. We discovered a dynamic serine-rich loop adjacent to the secondary pocket in the photolyase homology region (PHR) domain that regulates differential binding of cryptochromes to the PAS domain core of CLOCK:BMAL1. Notably, binding of the co-repressor PER2 remodels the serine loop of CRY2, making it more CRY1-like and enhancing its affinity for CLOCK:BMAL1.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

Lamellipodin tunes cell migration by stabilizing protrusions and promoting adhesion formation - Dimchev, Georgi A; Amiri, Behnam; Humphries, Ashley C.; Schaks, Matthias; Dimchev, Vanessa; Stradal, Theresia E. B.; Faix, Jan; Krause, Matthias; Way, Michael; Falcke, Martin; Rottner, Klemens (Journal of Cell Science)
Efficient migration on adhesive surfaces involves the protrusion of lamellipodial actin networks and their subsequent stabilization by nascent adhesions. The actin-binding protein lamellipodin (Lpd) is thought to play a critical role in lamellipodium protrusion, by delivering Ena/VASP proteins onto the growing plus ends of actin filaments and by interacting with the WAVE regulatory complex, an activator of the Arp2/3 complex, at the leading edge. Using B16-F1 melanoma cell lines, we demonstrate that genetic ablation of Lpd compromises protrusion efficiency and coincident cell migration without altering essential parameters of lamellipodia, including their maximal rate of forward advancement and actin polymerization. We also confirmed lamellipodia and migration phenotypes with CRISPR/Cas9-mediated Lpd knockout Rat2 fibroblasts, excluding cell type-specific effects. Moreover, computer-aided analysis of cell-edge morphodynamics on B16-F1 cell lamellipodia revealed that loss of Lpd correlates with reduced temporal protrusion maintenance as a prerequisite of nascent adhesion formation. We conclude that Lpd optimizes protrusion and nascent adhesion formation by counteracting frequent, chaotic retraction and membrane ruffling.This article has an associated First Person interview with the first author of the paper.
Keywords: Cell Biology

Changes in ESCRT-III filament geometry drive membrane remodelling and fission in silico - Harker-Kirschneck, Lena; Baum, Buzz; Šarić, Anđela (BMC Biology)
Background ESCRT-III is a membrane remodelling filament with the unique ability to cut membranes from the inside of the membrane neck. It is essential for the final stage of cell division, the formation of vesicles, the release of viruses, and membrane repair. Distinct from other cytoskeletal filaments, ESCRT-III filaments do not consume energy themselves, but work in conjunction with another ATP-consuming complex. Despite rapid progress in describing the cell biology of ESCRT-III, we lack an understanding of the physical mechanisms behind its force production and membrane remodelling. Results Here we present a minimal coarse-grained model that captures all the experimentally reported cases of ESCRT-III driven membrane sculpting, including the formation of downward and upward cones and tubules. This model suggests that a change in the geometry of membrane bound ESCRT-III filaments—from a flat spiral to a 3D helix—drives membrane deformation. We then show that such repetitive filament geometry transitions can induce the fission of cargo-containing vesicles. Conclusions Our model provides a general physical mechanism that explains the full range of ESCRT-III-dependent membrane remodelling and scission events observed in cells. This mechanism for filament force production is distinct from the mechanisms described for other cytoskeletal elements discovered so far. The mechanistic principles revealed here suggest new ways of manipulating ESCRT-III-driven processes in cells and could be used to guide the engineering of synthetic membrane-sculpting systems.
Keywords: cell biology

Minimal coarse-grained models for molecular self-organisation in biology - Hafner, Anne E; Krausser, Johannes; Šarić, Anđela (Current Opinion in Structural Biology)
The molecular machinery of life is largely created via self-organisation of individual molecules into functional assemblies. Minimal coarse-grained models, in which a whole macromolecule is represented by a small number of particles, can be of great value in identifying the main driving forces behind self-organisation in cell biology. Such models can incorporate data from both molecular and continuum scales, and their results can be directly compared to experiments. Here we review the state of the art of models for studying the formation and biological function of macromolecular assemblies in living organisms. We outline the key ingredients of each model and their main findings. We illustrate the contribution of this class of simulations to identifying the physical mechanisms behind life and diseases, and discuss their future developments.
Keywords: molecular biology; structural biology

Visualization of long-lived proteins reveals age mosaicism within nuclei of postmitotic cells - Toyama, Brandon H.; Arrojo e Drigo, Rafael; Lev-Ram, Varda; Ramachandra, Ranjan; Deerinck, Thomas J.; Lechene, Claude; Ellisman, Mark H.; HETZER, Martin W (Journal of Cell Biology)
Many adult tissues contain postmitotic cells as old as the host organism. The only organelle that does not turn over in these cells is the nucleus, and its maintenance represents a formidable challenge, as it harbors regulatory proteins that persist throughout adulthood. Here we developed strategies to visualize two classes of such long-lived proteins, histones and nucleoporins, to understand the function of protein longevity in nuclear maintenance. Genome-wide mapping of histones revealed specific enrichment of long-lived variants at silent gene loci. Interestingly, nuclear pores are maintained by piecemeal replacement of subunits, resulting in mosaic complexes composed of polypeptides with vastly different ages. In contrast, nondividing quiescent cells remove old nuclear pores in an ESCRT-dependent manner. Our findings reveal distinct molecular strategies of nuclear maintenance, linking lifelong protein persistence to gene regulation and nuclear integrity.
Keywords: Cell Biology

Age mosaicism across multiple scales in adult tissues - Arrojo e Drigo, Rafael; Lev-Ram, Varda; Tyagi, Swati; Ramachandra, Ranjan; Deerinck, Thomas; Bushong, Eric; Phan, Sebastien; Orphan, Victoria; Lechene, Claude; Ellisman, Mark H.; HETZER, Martin W (Cell Metabolism)
Most neurons are not replaced during an animal’s lifetime. This nondividing state is characterized by extreme longevity and age-dependent decline of key regulatory proteins. To study the lifespans of cells and proteins in adult tissues, we combined isotope labeling of mice with a hybrid imaging method (MIMS-EM). Using 15N mapping, we show that liver and pancreas are composed of cells with vastly different ages, many as old as the animal. Strikingly, we also found that a subset of fibroblasts and endothelial cells, both known for their replicative potential, are characterized by the absence of cell division during adulthood. In addition, we show that the primary cilia of beta cells and neurons contains different structural regions with vastly different lifespans. Based on these results, we propose that age mosaicism across multiple scales is a fundamental principle of adult tissue, cell, and protein complex organization.
Keywords: Cell Biology; Molecular Biology; Physiology

Coaching from the sidelines: The nuclear periphery in genome regulation - Buchwalter, Abigail; Kaneshiro, Jeanae M.; HETZER, Martin W (Nature Reviews Genetics)
The genome is packaged and organized nonrandomly within the 3D space of the nucleus to promote efficient gene expression and to faithfully maintain silencing of heterochromatin. The genome is enclosed within the nucleus by the nuclear envelope membrane, which contains a set of proteins that actively participate in chromatin organization and gene regulation. Technological advances are providing views of genome organization at unprecedented resolution and are beginning to reveal the ways that cells co-opt the structures of the nuclear periphery for nuclear organization and gene regulation. These genome regulatory roles of proteins of the nuclear periphery have important influences on development, disease and ageing.
Keywords: Genetics (clinical); Genetics; Molecular Biology

Integrated NMR and cryo-EM atomic-resolution structure determination of a half-megadalton enzyme complex - Gauto, Diego F.; Estrozi, Leandro F.; Schwieters, Charles D.; Effantin, Gregory; Macek, Pavel; Sounier, Remy; Sivertsen, Astrid C.; Schmidt, Elena; Kerfah, Rime; Mas, Guillaume; Colletier, Jacques-Philippe; Güntert, Peter; et al. (Nature Communications)
Atomic-resolution structure determination is crucial for understanding protein function. Cryo-EM and NMR spectroscopy both provide structural information, but currently cryo-EM does not routinely give access to atomic-level structural data, and, generally, NMR structure determination is restricted to small (<30 kDa) proteins. We introduce an integrated structure determination approach that simultaneously uses NMR and EM data to overcome the limits of each of these methods. The approach enables structure determination of the 468 kDa large dodecameric aminopeptidase TET2 to a precision and accuracy below 1 Å by combining secondary-structure information obtained from near-complete magic-angle-spinning NMR assignments of the 39 kDa-large subunits, distance restraints from backbone amides and ILV methyl groups, and a 4.1 Å resolution EM map. The resulting structure exceeds current standards of NMR and EM structure determination in terms of molecular weight and precision. Importantly, the approach is successful even in cases where only medium-resolution cryo-EM data are available.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Physics and Astronomy; General Chemistry

Studying intact bacterial peptidoglycan by proton-detected NMR spectroscopy at 100 kHz MAS frequency - Bougault, Catherine; Ayala, Isabel; Vollmer, Waldemar; Simorre, Jean-Pierre; Schanda, Paul (Journal of Structural Biology)
The bacterial cell wall is composed of the peptidoglycan (PG), a large polymer that maintains the integrity of the bacterial cell. Due to its multi-gigadalton size, heterogeneity, and dynamics, atomic-resolution studies are inherently complex. Solid-state NMR is an important technique to gain insight into its structure, dynamics and interactions. Here, we explore the possibilities to study the PG with ultra-fast (100 kHz) magic-angle spinning NMR. We demonstrate that highly resolved spectra can be obtained, and show strategies to obtain site-specific resonance assignments and distance information. We also explore the use of proton-proton correlation experiments, thus opening the way for NMR studies of intact cell walls without the need for isotope labeling.
Keywords: Structural Biology

Activity-controlled annealing of colloidal monolayers - Ramananarivo, Sophie; Ducrot, Etienne; Palacci, Jérémie A (Nature Communications)
Molecular motors are essential to the living, generating fluctuations that boost transport and assist assembly. Active colloids, that consume energy to move, hold similar potential for man-made materials controlled by forces generated from within. Yet, their use as a powerhouse in materials science lacks. Here we show a massive acceleration of the annealing of a monolayer of passive beads by moderate addition of self-propelled microparticles. We rationalize our observations with a model of collisions that drive active fluctuations and activate the annealing. The experiment is quantitatively compared with Brownian dynamic simulations that further unveil a dynamical transition in the mechanism of annealing. Active dopants travel uniformly in the system or co-localize at the grain boundaries as a result of the persistence of their motion. Our findings uncover the potential of internal activity to control materials and lay the groundwork for the rise of materials science beyond equilibrium.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Physics and Astronomy; General Chemistry

Design on a rational basis of high-affinity peptides inhibiting the histone chaperone ASF1 - Bakail, May M; Gaubert, Albane; Andreani, Jessica; Moal, Gwenaëlle; Pinna, Guillaume; Boyarchuk, Ekaterina; Gaillard, Marie-Cécile; Courbeyrette, Regis; Mann, Carl; Thuret, Jean-Yves; Guichard, Bérengère; Murciano, Brice; et al. (Cell Chemical Biology)
Anti-silencing function 1 (ASF1) is a conserved H3-H4 histone chaperone involved in histone dynamics during replication, transcription, and DNA repair. Overexpressed in proliferating tissues including many tumors, ASF1 has emerged as a promising therapeutic target. Here, we combine structural, computational, and biochemical approaches to design peptides that inhibit the ASF1-histone interaction. Starting from the structure of the human ASF1-histone complex, we developed a rational design strategy combining epitope tethering and optimization of interface contacts to identify a potent peptide inhibitor with a dissociation constant of 3 nM. When introduced into cultured cells, the inhibitors impair cell proliferation, perturb cell-cycle progression, and reduce cell migration and invasion in a manner commensurate with their affinity for ASF1. Finally, we find that direct injection of the most potent ASF1 peptide inhibitor in mouse allografts reduces tumor growth. Our results open new avenues to use ASF1 inhibitors as promising leads for cancer therapy.
Keywords: Clinical Biochemistry; Molecular Medicine; Biochemistry; Molecular Biology; Pharmacology; Drug Discovery

Natural depletion of histone H1 in sex cells causes DNA demethylation, heterochromatin decondensation and transposon activation - He, Shengbo; Vickers, Martin; Zhang, Jingyi; Feng, Xiaoqi (eLife)
Transposable elements (TEs), the movement of which can damage the genome, are epigenetically silenced in eukaryotes. Intriguingly, TEs are activated in the sperm companion cell – vegetative cell (VC) – of the flowering plant Arabidopsis thaliana. However, the extent and mechanism of this activation are unknown. Here we show that about 100 heterochromatic TEs are activated in VCs, mostly by DEMETER-catalyzed DNA demethylation. We further demonstrate that DEMETER access to some of these TEs is permitted by the natural depletion of linker histone H1 in VCs. Ectopically expressed H1 suppresses TEs in VCs by reducing DNA demethylation and via a methylation-independent mechanism. We demonstrate that H1 is required for heterochromatin condensation in plant cells and show that H1 overexpression creates heterochromatic foci in the VC progenitor cell. Taken together, our results demonstrate that the natural depletion of H1 during male gametogenesis facilitates DEMETER-directed DNA demethylation, heterochromatin relaxation, and TE activation.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

Natural variation in TBP-ASSOCIATED FACTOR 4b controls meiotic crossover and germline transcription in Arabidopsis - Lawrence, Emma J.; Gao, Hongbo; Tock, Andrew J.; Lambing, Christophe; Blackwell, Alexander R.; Feng, Xiaoqi; Henderson, Ian R. (Current Biology)
Meiotic crossover frequency varies within genomes, which influences genetic diversity and adaptation. In turn, genetic variation within populations can act to modify crossover frequency in cis and trans. To identify genetic variation that controls meiotic crossover frequency, we screened Arabidopsis accessions using fluorescent recombination reporters. We mapped a genetic modifier of crossover frequency in Col × Bur populations of Arabidopsis to a premature stop codon within TBP-ASSOCIATED FACTOR 4b (TAF4b), which encodes a subunit of the RNA polymerase II general transcription factor TFIID. The Arabidopsis taf4b mutation is a rare variant found in the British Isles, originating in South-West Ireland. Using genetics, genomics, and immunocytology, we demonstrate a genome-wide decrease in taf4b crossovers, with strongest reduction in the sub-telomeric regions. Using RNA sequencing (RNA-seq) from purified meiocytes, we show that TAF4b expression is meiocyte enriched, whereas its paralog TAF4 is broadly expressed. Consistent with the role of TFIID in promoting gene expression, RNA-seq of wild-type and taf4b meiocytes identified widespread transcriptional changes, including in genes that regulate the meiotic cell cycle and recombination. Therefore, TAF4b duplication is associated with acquisition of meiocyte-specific expression and promotion of germline transcription, which act directly or indirectly to elevate crossovers. This identifies a novel mode of meiotic recombination control via a general transcription factor.
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology

Selective clearance of the inner nuclear membrane protein emerin by vesicular transport during ER stress - Buchwalter, Abigail; Schulte, Roberta; Tsai, Hsiao; Capitanio, Juliana; HETZER, Martin W (eLife)
The inner nuclear membrane (INM) is a subdomain of the endoplasmic reticulum (ER) that is gated by the nuclear pore complex. It is unknown whether proteins of the INM and ER are degraded through shared or distinct pathways in mammalian cells. We applied dynamic proteomics to profile protein half-lives and report that INM and ER residents turn over at similar rates, indicating that the INM’s unique topology is not a barrier to turnover. Using a microscopy approach, we observed that the proteasome can degrade INM proteins in situ. However, we also uncovered evidence for selective, vesicular transport-mediated turnover of a single INM protein, emerin, that is potentiated by ER stress. Emerin is rapidly cleared from the INM by a mechanism that requires emerin’s LEM domain to mediate vesicular trafficking to lysosomes. This work demonstrates that the INM can be dynamically remodeled in response to environmental inputs.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

The implication of cytoskeletal dynamics on leukocyte migration - Kopf, Aglaja
While cells of mesenchymal or epithelial origin perform their effector functions in a purely anchorage dependent manner, cells derived from the hematopoietic lineage are not committed to operate only within a specific niche. Instead, these cells are able to function autonomously of the molecular composition in a broad range of tissue compartments. By this means, cells of the hematopoietic lineage retain the capacity to disseminate into connective tissue and recirculate between organs, building the foundation for essential processes such as tissue regeneration or immune surveillance. Cells of the immune system, specifically leukocytes, are extraordinarily good at performing this task. These cells are able to flexibly shift their mode of migration between an adhesion-mediated and an adhesion-independent manner, instantaneously accommodating for any changes in molecular composition of the external scaffold. The key component driving directed leukocyte migration is the chemokine receptor 7, which guides the cell along gradients of chemokine ligand. Therefore, the physical destination of migrating leukocytes is purely deterministic, i.e. given by global directional cues such as chemokine gradients. Nevertheless, these cells typically reside in three-dimensional scaffolds of inhomogeneous complexity, raising the question whether cells are able to locally discriminate between multiple optional migration routes. Current literature provides evidence that leukocytes, specifically dendritic cells, do indeed probe their surrounding by virtue of multiple explorative protrusions. However, it remains enigmatic how these cells decide which one is the more favorable route to follow and what are the key players involved in performing this task. Due to the heterogeneous environment of most tissues, and the vast adaptability of migrating leukocytes, at this time it is not clear to what extent leukocytes are able to optimize their migratory strategy by adapting their level of adhesiveness. And, given the fact that leukocyte migration is characterized by branched cell shapes in combination with high migration velocities, it is reasonable to assume that these cells require fine tuned shape maintenance mechanisms that tightly coordinate protrusion and adhesion dynamics in a spatiotemporal manner. Therefore, this study aimed to elucidate how rapidly migrating leukocytes opt for an ideal migratory path while maintaining a continuous cell shape and balancing adhesive forces to efficiently navigate through complex microenvironments. The results of this study unraveled a role for the microtubule cytoskeleton in promoting the decision making process during path finding and for the first time point towards a microtubule-mediated function in cell shape maintenance of highly ramified cells such as dendritic cells. Furthermore, we found that migrating low-adhesive leukocytes are able to instantaneously adapt to increased tensile load by engaging adhesion receptors. This response was only occurring tangential to the substrate while adhesive properties in the vertical direction were not increased. As leukocytes are primed for rapid migration velocities, these results demonstrate that leukocyte integrins are able to confer a high level of traction forces parallel to the cell membrane along the direction of migration without wasting energy in gluing the cell to the substrate. Thus, the data in the here presented thesis provide new insights into the pivotal role of cytoskeletal dynamics and the mechanisms of force transduction during leukocyte migration. Thereby the here presented results help to further define fundamental principles underlying leukocyte migration and open up potential therapeutic avenues of clinical relevance.
Keywords: cell biology; immunology; leukocyte; migration; microfluidics

Tpr regulates the total number of nuclear pore complexes per cell nucleus - McCloskey, Asako; Ibarra, Arkaitz; HETZER, Martin W (Genes & Development)
The total number of nuclear pore complexes (NPCs) per nucleus varies greatly between different cell types and is known to change during cell differentiation and cell transformation. However, the underlying mechanisms that control how many nuclear transport channels are assembled into a given nuclear envelope remain unclear. Here, we report that depletion of the NPC basket protein Tpr, but not Nup153, dramatically increases the total NPC number in various cell types. This negative regulation of Tpr occurs via a phosphorylation cascade of extracellular signal-regulated kinase (ERK), the central kinase of the mitogen-activated protein kinase (MAPK) pathway. Tpr serves as a scaffold for ERK to phosphorylate the nucleoporin (Nup) Nup153, which is critical for early stages of NPC biogenesis. Our results reveal a critical role of the Nup Tpr in coordinating signal transduction pathways during cell proliferation and the dynamic organization of the nucleus.
Keywords: Developmental Biology; Genetics

The antibiotic cyclomarin blocks arginine-phosphate–induced millisecond dynamics in the N-terminal domain of ClpC1 from Mycobacterium tuberculosis - Weinhäupl, Katharina; Brennich, Martha; Kazmaier, Uli; Lelievre, Joel; Ballell, Lluis; Goldberg, Alfred; Schanda, Paul; Fraga, Hugo (Journal of Biological Chemistry)
Mycobacterium tuberculosis can remain dormant in the host, an ability that explains the failure of many current tuberculosis treatments. Recently, the natural products cyclomarin, ecumicin, and lassomycin have been shown to efficiently kill Mycobacterium tuberculosis persisters. Their target is the N-terminal domain of the hexameric AAA+ ATPase ClpC1, which recognizes, unfolds, and translocates protein substrates, such as proteins containing phosphorylated arginine residues, to the ClpP1P2 protease for degradation. Surprisingly, these antibiotics do not inhibit ClpC1 ATPase activity, and how they cause cell death is still unclear. Here, using NMR and small-angle X-ray scattering, we demonstrate that arginine-phosphate binding to the ClpC1 N-terminal domain induces millisecond dynamics. We show that these dynamics are caused by conformational changes and do not result from unfolding or oligomerization of this domain. Cyclomarin binding to this domain specifically blocked these N-terminal dynamics. On the basis of these results, we propose a mechanism of action involving cyclomarin-induced restriction of ClpC1 dynamics, which modulates the chaperone enzymatic activity leading eventually to cell death.
Keywords: Cell Biology; Biochemistry; Molecular Biology

Structural basis of membrane protein chaperoning through the mitochondrial intermembrane space - Weinhäupl, Katharina; Lindau, Caroline; Hessel, Audrey; Wang, Yong; Schütze, Conny; Jores, Tobias; Melchionda, Laura; Schönfisch, Birgit; Kalbacher, Hubert; Bersch, Beate; Rapaport, Doron; Brennich, Martha; et al. (Cell)
The exchange of metabolites between the mitochondrial matrix and the cytosol depends on β-barrel channels in the outer membrane and α-helical carrier proteins in the inner membrane. The essential translocase of the inner membrane (TIM) chaperones escort these proteins through the intermembrane space, but the structural and mechanistic details remain elusive. We have used an integrated structural biology approach to reveal the functional principle of TIM chaperones. Multiple clamp-like binding sites hold the mitochondrial membrane proteins in a translocation-competent elongated form, thus mimicking characteristics of co-translational membrane insertion. The bound preprotein undergoes conformational dynamics within the chaperone binding clefts, pointing to a multitude of dynamic local binding events. Mutations in these binding sites cause cell death or growth defects associated with impairment of carrier and β-barrel protein biogenesis. Our work reveals how a single mitochondrial “transfer-chaperone” system is able to guide α-helical and β-barrel membrane proteins in a “nascent chain-like” conformation through a ribosome-free compartment.
Keywords: General Biochemistry; Genetics and Molecular Biology

Dynamics and interactions of AAC3 in DPC are not functionally relevant - Kurauskas, Vilius; Hessel, Audrey; Dehez, François; Chipot, Christophe; Bersch, Beate; Schanda, Paul (Nature Structural & Molecular Biology)
Keywords: Molecular Biology; Structural Biology

Reversible chromism of spiropyran in the cavity of a flexible coordination cage - Samanta, Dipak; Galaktionova, Daria; Gemen, Julius; Shimon, Linda J. W.; Diskin-Posner, Yael; Avram, Liat; Král, Petr; Klajn, Rafal (Nature Communications)
Confining molecules to volumes only slightly larger than the molecules themselves can profoundly alter their properties. Molecular switches—entities that can be toggled between two or more forms upon exposure to an external stimulus—often require conformational freedom to isomerize. Therefore, placing these switches in confined spaces can render them non-operational. To preserve the switchability of these species under confinement, we work with a water-soluble coordination cage that is flexible enough to adapt its shape to the conformation of the encapsulated guest. We show that owing to its flexibility, the cage is not only capable of accommodating—and solubilizing in water—several light-responsive spiropyran-based molecular switches, but, more importantly, it also provides an environment suitable for the efficient, reversible photoisomerization of the bound guests. Our findings pave the way towards studying various molecular switching processes in confined environments.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Significance of whole-genome duplications on the emergence of evolutionary novelties - Yuuta, Moriyama; Koshiba-Takeuchi, Kazuko (Briefings in Functional Genomics)
Acquisition of evolutionary novelties is a fundamental process for adapting to the external environment and invading new niches and results in the diversification of life, which we can see in the world today. How such novel phenotypic traits are acquired in the course of evolution and are built up in developing embryos has been a central question in biology. Whole-genome duplication (WGD) is a process of genome doubling that supplies raw genetic materials and increases genome complexity. Recently, it has been gradually revealed that WGD and subsequent fate changes of duplicated genes can facilitate phenotypic evolution. Here, we review the current understanding of the relationship between WGD and the acquisition of evolutionary novelties. We show some examples of this link and discuss how WGD and subsequent duplicated genes can facilitate phenotypic evolution as well as when such genomic doubling can be advantageous for adaptation.
Keywords: Genetics; Molecular Biology; Biochemistry; General Medicine

Structure and mechanism of the two-component α-helical pore-forming toxin YaxAB - Bräuning, Bastian; Bertosin, Eva; Praetorius, Florian M; Ihling, Christian; Schatt, Alexandra; Adler, Agnes; Richter, Klaus; Sinz, Andrea; Dietz, Hendrik; Groll, Michael (Nature Communications)
Pore-forming toxins (PFT) are virulence factors that transform from soluble to membrane-bound states. The Yersinia YaxAB system represents a family of binary α-PFTs with orthologues in human, insect, and plant pathogens, with unknown structures. YaxAB was shown to be cytotoxic and likely involved in pathogenesis, though the molecular basis for its two-component lytic mechanism remains elusive. Here, we present crystal structures of YaxA and YaxB, together with a cryo-electron microscopy map of the YaxAB complex. Our structures reveal a pore predominantly composed of decamers of YaxA–YaxB heterodimers. Both subunits bear membrane-active moieties, but only YaxA is capable of binding to membranes by itself. YaxB can subsequently be recruited to membrane-associated YaxA and induced to present its lytic transmembrane helices. Pore formation can progress by further oligomerization of YaxA–YaxB dimers. Our results allow for a comparison between pore assemblies belonging to the wider ClyA-like family of α-PFTs, highlighting diverse pore architectures.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Mechanical force induces mitochondrial fission - Helle, Sebastian Carsten Johannes; Feng, Qian; Aebersold, Mathias J; Hirt, Luca; Grüter, Raphael R; Vahid, Afshin; Sirianni, Andrea; Mostowy, Serge; Snedeker, Jess G; Šarić, Anđela; Idema, Timon; Zambelli, Tomaso; et al. (eLife)
Eukaryotic cells are densely packed with macromolecular complexes and intertwining organelles, continually transported and reshaped. Intriguingly, organelles avoid clashing and entangling with each other in such limited space. Mitochondria form extensive networks constantly remodeled by fission and fusion. Here, we show that mitochondrial fission is triggered by mechanical forces. Mechano-stimulation of mitochondria – via encounter with motile intracellular pathogens, via external pressure applied by an atomic force microscope, or via cell migration across uneven microsurfaces – results in the recruitment of the mitochondrial fission machinery, and subsequent division. We propose that MFF, owing to affinity for narrow mitochondria, acts as a membrane-bound force sensor to recruit the fission machinery to mechanically strained sites. Thus, mitochondria adapt to the environment by sensing and responding to biomechanical cues. Our findings that mechanical triggers can be coupled to biochemical responses in membrane dynamics may explain how organelles orderly cohabit in the crowded cytoplasm.
Keywords: general immunology and microbiology; general biochemistry; genetics and molecular biology; general medicine; general neuroscience

Nup98 recruits the Wdr82–Set1A/COMPASS complex to promoters to regulate H3K4 trimethylation in hematopoietic progenitor cells - Franks, Tobias M.; McCloskey, Asako; Shokhirev, Maxim Nikolaievich; Benner, Chris; Rathore, Annie; HETZER, Martin W (Genes & Development)
Recent studies have shown that a subset of nucleoporins (Nups) can detach from the nuclear pore complex and move into the nuclear interior to regulate transcription. One such dynamic Nup, called Nup98, has been implicated in gene activation in healthy cells and has been shown to drive leukemogenesis when mutated in patients with acute myeloid leukemia (AML). Here we show that in hematopoietic cells, Nup98 binds predominantly to transcription start sites to recruit the Wdr82–Set1A/COMPASS (complex of proteins associated with Set1) complex, which is required for deposition of the histone 3 Lys4 trimethyl (H3K4me3)-activating mark. Depletion of Nup98 or Wdr82 abolishes Set1A recruitment to chromatin and subsequently ablates H3K4me3 at adjacent promoters. Furthermore, expression of a Nup98 fusion protein implicated in aggressive AML causes mislocalization of H3K4me3 at abnormal regions and up-regulation of associated genes. Our findings establish a function of Nup98 in hematopoietic gene activation and provide mechanistic insight into which Nup98 leukemic fusion proteins promote AML.
Keywords: Developmental Biology; Genetics

Nup153 interacts with Sox2 to enable bimodal gene regulation and maintenance of neural progenitor cells - Toda, Tomohisa; Hsu, Jonathan Y.; Linker, Sara B.; Hu, Lauren; Schafer, Simon T.; Mertens, Jerome; Jacinto, Filipe V.; HETZER, Martin W; Gage, Fred H. (Cell Stem Cell)
Neural progenitor cells (NeuPCs) possess a unique nuclear architecture that changes during differentiation. Nucleoporins are linked with cell-type-specific gene regulation, coupling physical changes in nuclear structure to transcriptional output; but, whether and how they coordinate with key fate-determining transcription factors is unclear. Here we show that the nucleoporin Nup153 interacts with Sox2 in adult NeuPCs, where it is indispensable for their maintenance and controls neuronal differentiation. Genome-wide analyses show that Nup153 and Sox2 bind and co-regulate hundreds of genes. Binding of Nup153 to gene promoters or transcriptional end sites correlates with increased or decreased gene expression, respectively, and inhibiting Nup153 expression alters open chromatin configurations at its target genes, disrupts genomic localization of Sox2, and promotes differentiation in vitro and a gliogenic fate switch in vivo. Together, these findings reveal that nuclear structural proteins may exert bimodal transcriptional effects to control cell fate.
Keywords: Cell Biology; Genetics; Molecular Medicine

Nucleolar expansion and elevated protein translation in premature aging - Buchwalter, Abigail; HETZER, Martin W (Nature Communications)
Premature aging disorders provide an opportunity to study the mechanisms that drive aging. In Hutchinson-Gilford progeria syndrome (HGPS), a mutant form of the nuclear scaffold protein lamin A distorts nuclei and sequesters nuclear proteins. We sought to investigate protein homeostasis in this disease. Here, we report a widespread increase in protein turnover in HGPS-derived cells compared to normal cells. We determine that global protein synthesis is elevated as a consequence of activated nucleoli and enhanced ribosome biogenesis in HGPS-derived fibroblasts. Depleting normal lamin A or inducing mutant lamin A expression are each sufficient to drive nucleolar expansion. We further show that nucleolar size correlates with donor age in primary fibroblasts derived from healthy individuals and that ribosomal RNA production increases with age, indicating that nucleolar size and activity can serve as aging biomarkers. While limiting ribosome biogenesis extends lifespan in several systems, we show that increased ribosome biogenesis and activity are a hallmark of premature aging.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

Dynamics of valence-shell electrons and nuclei probed by strong-field holography and rescattering - Walt, Samuel G.; Bhargava Ram, Niraghatam; Atala, Marcos; Shvetsov-Shilovski, Nikolay I; von Conta, Aaron; Baykusheva, Denitsa Rangelova; Lein, Manfred; Wörner, Hans Jakob (Nature Communications)
Strong-field photoelectron holography and laser-induced electron diffraction (LIED) are two powerful emerging methods for probing the ultrafast dynamics of molecules. However, both of them have remained restricted to static systems and to nuclear dynamics induced by strong-field ionization. Here we extend these promising methods to image purely electronic valence-shell dynamics in molecules using photoelectron holography. In the same experiment, we use LIED and photoelectron holography simultaneously, to observe coupled electronic-rotational dynamics taking place on similar timescales. These results offer perspectives for imaging ultrafast dynamics of molecules on femtosecond to attosecond timescales.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Structural dynamics of RbmA governs plasticity of Vibrio cholerae biofilms - Fong, Jiunn CN; Rogers, Andrew; Michael, Alicia Kathleen; Parsley, Nicole C; Cornell, William-Cole; Lin, Yu-Cheng; Singh, Praveen K; Hartmann, Raimo; Drescher, Knut; Vinogradov, Evgeny; Dietrich, Lars EP; Partch, Carrie L; et al. (eLife)
Biofilm formation is critical for the infection cycle of Vibrio cholerae. Vibrio exopolysaccharides (VPS) and the matrix proteins RbmA, Bap1 and RbmC are required for the development of biofilm architecture. We demonstrate that RbmA binds VPS directly and uses a binary structural switch within its first fibronectin type III (FnIII-1) domain to control RbmA structural dynamics and the formation of VPS-dependent higher-order structures. The structural switch in FnIII-1 regulates interactions in trans with the FnIII-2 domain, leading to open (monomeric) or closed (dimeric) interfaces. The ability of RbmA to switch between open and closed states is important for V. cholerae biofilm formation, as RbmA variants with switches that are locked in either of the two states lead to biofilms with altered architecture and structural integrity.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

A slow conformational switch in the BMAL1 transactivation domain modulates circadian rhythms - Gustafson, Chelsea L.; Parsley, Nicole C.; Asimgil, Hande; Lee, Hsiau-Wei; Ahlbach, Christopher; Michael, Alicia Kathleen; Xu, Haiyan; Williams, Owen L.; Davis, Tara L.; Liu, Andrew C.; Partch, Carrie L. (Molecular Cell)
The C-terminal transactivation domain (TAD) of BMAL1 (brain and muscle ARNT-like 1) is a regulatory hub for transcriptional coactivators and repressors that compete for binding and, consequently, contributes to period determination of the mammalian circadian clock. Here, we report the discovery of two distinct conformational states that slowly exchange within the dynamic TAD to control timing. This binary switch results from cis/trans isomerization about a highly conserved Trp-Pro imide bond in a region of the TAD that is required for normal circadian timekeeping. Both cis and trans isomers interact with transcriptional regulators, suggesting that isomerization could serve a role in assembling regulatory complexes in vivo. Toward this end, we show that locking the switch into the trans isomer leads to shortened circadian periods. Furthermore, isomerization is regulated by the cyclophilin family of peptidyl-prolyl isomerases, highlighting the potential for regulation of BMAL1 protein dynamics in period determination.
Keywords: Cell Biology; Molecular Biology

p120-catenin prevents multinucleation through control of MKLP1-dependent RhoA activity during cytokinesis - van de Ven, Robert A.H.; de Groot, Jolien S.; Park, Danielle; van Domselaar, Robert; de Jong, Danielle; Szuhai, Karoly; van der Wall, Elsken; Rueda, Oscar M.; Ali, H. Raza; Caldas, Carlos; van Diest, Paul J.; HETZER, Martin W; et al. (Nature Communications)
Spatiotemporal activation of RhoA and actomyosin contraction underpins cellular adhesion and division. Loss of cell–cell adhesion and chromosomal instability are cardinal events that drive tumour progression. Here, we show that p120-catenin (p120) not only controls cell–cell adhesion, but also acts as a critical regulator of cytokinesis. We find that p120 regulates actomyosin contractility through concomitant binding to RhoA and the centralspindlin component MKLP1, independent of cadherin association. In anaphase, p120 is enriched at the cleavage furrow where it binds MKLP1 to spatially control RhoA GTPase cycling. Binding of p120 to MKLP1 during cytokinesis depends on the N-terminal coiled-coil domain of p120 isoform 1A. Importantly, clinical data show that loss of p120 expression is a common event in breast cancer that strongly correlates with multinucleation and adverse patient survival. In summary, our study identifies p120 loss as a driver event of chromosomal instability in cancer.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

Evolution of a transcriptional regulator from a transmembrane nucleoporin - Franks, Tobias M.; Benner, Chris; Narvaiza, Iñigo; Marchetto, Maria C.N.; Young, Janet M.; Malik, Harmit S.; Gage, Fred H.; HETZER, Martin W (Genes & Development)
Nuclear pore complexes (NPCs) emerged as nuclear transport channels in eukaryotic cells ∼1.5 billion years ago. While the primary role of NPCs is to regulate nucleo–cytoplasmic transport, recent research suggests that certain NPC proteins have additionally acquired the role of affecting gene expression at the nuclear periphery and in the nucleoplasm in metazoans. Here we identify a widely expressed variant of the transmembrane nucleoporin (Nup) Pom121 (named sPom121, for “soluble Pom121”) that arose by genomic rearrangement before the divergence of hominoids. sPom121 lacks the nuclear membrane-anchoring domain and thus does not localize to the NPC. Instead, sPom121 colocalizes and interacts with nucleoplasmic Nup98, a previously identified transcriptional regulator, at gene promoters to control transcription of its target genes in human cells. Interestingly, sPom121 transcripts appear independently in several mammalian species, suggesting convergent innovation of Nup-mediated transcription regulation during mammalian evolution. Our findings implicate alternate transcription initiation as a mechanism to increase the functional diversity of NPC components.
Keywords: Developmental Biology; Genetics

Nuclear envelope rupture is induced by actin-based nucleus confinement - Hatch, Emily M.; HETZER, Martin W (Journal of Cell Biology)
Repeated rounds of nuclear envelope (NE) rupture and repair have been observed in laminopathy and cancer cells and result in intermittent loss of nucleus compartmentalization. Currently, the causes of NE rupture are unclear. Here, we show that NE rupture in cancer cells relies on the assembly of contractile actin bundles that interact with the nucleus via the linker of nucleoskeleton and cytoskeleton (LINC) complex. We found that the loss of actin bundles or the LINC complex did not rescue nuclear lamina defects, a previously identified determinant of nuclear membrane stability, but did decrease the number and size of chromatin hernias. Finally, NE rupture inhibition could be rescued in cells treated with actin-depolymerizing drugs by mechanically constraining nucleus height. These data suggest a model of NE rupture where weak membrane areas, caused by defects in lamina organization, rupture because of an increase in intranuclear pressure from actin-based nucleus confinement.
Keywords: Cell Biology

Nucleoporin-mediated regulation of cell identity genes - Ibarra, Arkaitz; Benner, Chris; Tyagi, Swati; Cool, Jonah; HETZER, Martin W (Genes & Development)
The organization of the genome in the three-dimensional space of the nucleus is coupled with cell type-specific gene expression. However, how nuclear architecture influences transcription that governs cell identity remains unknown. Here, we show that nuclear pore complex (NPC) components Nup93 and Nup153 bind superenhancers (SE), regulatory structures that drive the expression of key genes that specify cell identity. We found that nucleoporin-associated SEs localize preferentially to the nuclear periphery, and absence of Nup153 and Nup93 results in dramatic transcriptional changes of SE-associated genes. Our results reveal a crucial role of NPC components in the regulation of cell type-specifying genes and highlight nuclear architecture as a regulatory layer of genome functions in cell fate.
Keywords: Developmental Biology; Genetics

Directly reprogrammed human neurons retain aging-associated transcriptomic signatures and reveal age-related nucleocytoplasmic defects - Mertens, Jerome; Paquola, Apuã C.M.; Ku, Manching; Hatch, Emily; Böhnke, Lena; Ladjevardi, Shauheen; McGrath, Sean; Campbell, Benjamin; Lee, Hyungjun; Herdy, Joseph R.; Gonçalves, J. Tiago; Toda, Tomohisa; et al. (Cell Stem Cell)
Aging is a major risk factor for many human diseases, and in vitro generation of human neurons is an attractive approach for modeling aging-related brain disorders. However, modeling aging in differentiated human neurons has proved challenging. We generated neurons from human donors across a broad range of ages, either by iPSC-based reprogramming and differentiation or by direct conversion into induced neurons (iNs). While iPSCs and derived neurons did not retain aging-associated gene signatures, iNs displayed age-specific transcriptional profiles and revealed age-associated decreases in the nuclear transport receptor RanBP17. We detected an age-dependent loss of nucleocytoplasmic compartmentalization (NCC) in donor fibroblasts and corresponding iNs and found that reduced RanBP17 impaired NCC in young cells, while iPSC rejuvenation restored NCC in aged cells. These results show that iNs retain important aging-related signatures, thus allowing modeling of the aging process in vitro, and they identify impaired NCC as an important factor in human aging.
Keywords: Cell Biology; Genetics; Molecular Medicine

The nucleoporin Nup153 regulates embryonic stem cell pluripotency through gene silencing - Jacinto, Filipe V.; Benner, Chris; HETZER, Martin W (Genes & Development)
Nucleoporins (Nups) are a family of proteins best known as the constituent building blocks of nuclear pore complexes (NPCs), membrane-embedded channels that mediate nuclear transport across the nuclear envelope. Recent evidence suggests that several Nups have additional roles in controlling the activation and silencing of developmental genes; however, the mechanistic details of these functions remain poorly understood. Here, we show that depletion of Nup153 in mouse embryonic stem cells (mESCs) causes the derepression of developmental genes and induction of early differentiation. This loss of stem cell identity is not associated with defects in the nuclear import of key pluripotency factors. Rather, Nup153 binds around the transcriptional start site (TSS) of developmental genes and mediates the recruitment of the polycomb-repressive complex 1 (PRC1) to a subset of its target loci. Our results demonstrate a chromatin-associated role of Nup153 in maintaining stem cell pluripotency by functioning in mammalian epigenetic gene silencing.
Keywords: Developmental Biology; Genetics

Integrated transcriptome and proteome analyses reveal organ-specific proteome deterioration in old rats - Ori, Alessandro; Toyama, Brandon H.; Harris, Michael S.; Bock, Thomas; Iskar, Murat; Bork, Peer; Ingolia, Nicholas T.; HETZER, Martin W; Beck, Martin (Cell Systems)
Aging is associated with the decline of protein, cell, and organ function. Here, we use an integrated approach to characterize gene expression, bulk translation, and cell biology in the brains and livers of young and old rats. We identify 468 differences in protein abundance between young and old animals. The majority are a consequence of altered translation output, that is, the combined effect of changes in transcript abundance and translation efficiency. In addition, we identify 130 proteins whose overall abundance remains unchanged but whose sub-cellular localization, phosphorylation state, or splice-form varies. While some protein-level differences appear to be a generic property of the rats’ chronological age, the majority are specific to one organ. These may be a consequence of the organ’s physiology or the chronological age of the cells within the tissue. Taken together, our study provides an initial view of the proteome at the molecular, sub-cellular, and organ level in young and old rats.
Keywords: Cell Biology; Histology; Pathology and Forensic Medicine

The nucleoporin gp210/Nup210 controls muscle differentiation by regulating nuclear envelope/ER homeostasis - Gomez-Cavazos, J. Sebastian; HETZER, Martin W (Journal of Cell Biology)
Previously, we identified the nucleoporin gp210/Nup210 as a critical regulator of muscle and neuronal differentiation, but how this nucleoporin exerts its function and whether it modulates nuclear pore complex (NPC) activity remain unknown. Here, we show that gp210/Nup210 mediates muscle cell differentiation in vitro via its conserved N-terminal domain that extends into the perinuclear space. Removal of the C-terminal domain, which partially mislocalizes gp210/Nup210 away from NPCs, efficiently rescues the differentiation defect caused by the knockdown of endogenous gp210/Nup210. Unexpectedly, a gp210/Nup210 mutant lacking the NPC-targeting transmembrane and C-terminal domains is sufficient for C2C12 myoblast differentiation. We demonstrate that the endoplasmic reticulum (ER) stress-specific caspase cascade is exacerbated during Nup210 depletion and that blocking ER stress-mediated apoptosis rescues differentiation of Nup210-deficient cells. Our results suggest that the role of gp210/Nup210 in cell differentiation is mediated by its large luminal domain, which can act independently of NPC association and appears to play a pivotal role in the maintenance of nuclear envelope/ER homeostasis.
Keywords: Cell Biology

Nuclear pore proteins and the control of genome functions - Ibarra, Arkaitz; HETZER, Martin W (Genes & Development)
Nuclear pore complexes (NPCs) are composed of several copies of ∼30 different proteins called nucleoporins (Nups). NPCs penetrate the nuclear envelope (NE) and regulate the nucleocytoplasmic trafficking of macromolecules. Beyond this vital role, NPC components influence genome functions in a transport-independent manner. Nups play an evolutionarily conserved role in gene expression regulation that, in metazoans, extends into the nuclear interior. Additionally, in proliferative cells, Nups play a crucial role in genome integrity maintenance and mitotic progression. Here we discuss genome-related functions of Nups and their impact on essential DNA metabolism processes such as transcription, chromosome duplication, and segregation.
Keywords: Developmental Biology; Genetics

Linking micronuclei to chromosome fragmentation - Hatch, Emily M.; HETZER, Martin W (Cell)
Human cancer cells bear complex chromosome rearrangements that can be potential drivers of cancer development. However, the molecular mechanisms underlying these rearrangements have been unclear. Zhang et al. use a new technique combining live-cell imaging and single-cell sequencing to demonstrate that chromosomes mis-segregated to micronuclei frequently undergo chromothripsis-like rearrangements in the subsequent cell cycle.
Keywords: General Biochemistry; Genetics and Molecular Biology

Chromothripsis - Hatch, Emily M.; HETZER, Martin W (Current Biology)
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology

Observing the overall rocking motion of a protein in a crystal - Ma, Peixiang; Xue, Yi; Coquelle, Nicolas; Haller, Jens D.; Yuwen, Tairan; Ayala, Isabel; Mikhailovskii, Oleg; Willbold, Dieter; Colletier, Jacques-Philippe; Skrynnikov, Nikolai R.; Schanda, Paul (Nature Communications)
The large majority of three-dimensional structures of biological macromolecules have been determined by X-ray diffraction of crystalline samples. High-resolution structure determination crucially depends on the homogeneity of the protein crystal. Overall ‘rocking’ motion of molecules in the crystal is expected to influence diffraction quality, and such motion may therefore affect the process of solving crystal structures. Yet, so far overall molecular motion has not directly been observed in protein crystals, and the timescale of such dynamics remains unclear. Here we use solid-state NMR, X-ray diffraction methods and μs-long molecular dynamics simulations to directly characterize the rigid-body motion of a protein in different crystal forms. For ubiquitin crystals investigated in this study we determine the range of possible correlation times of rocking motion, 0.1–100 μs. The amplitude of rocking varies from one crystal form to another and is correlated with the resolution obtainable in X-ray diffraction experiments.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Physics and Astronomy; General Chemistry

The chromatin remodeler SPLAYED negatively regulates SNC1-mediated immunity - Johnson, Kaeli C.M.; Xia, Shitou; Feng, Xiaoqi; Li, Xin (Plant and Cell Physiology)
SNC1 (SUPPRESSOR OF NPR1, CONSTITUTIVE 1) is one of a suite of intracellular Arabidopsis NOD-like receptor (NLR) proteins which, upon activation, result in the induction of defense responses. However, the molecular mechanisms underlying NLR activation and the subsequent provocation of immune responses are only partially characterized. To identify negative regulators of NLR-mediated immunity, a forward genetic screen was undertaken to search for enhancers of the dwarf, autoimmune gain-of-function snc1 mutant. To avoid lethality resulting from severe dwarfism, the screen was conducted using mos4 (modifier of snc1, 4) snc1 plants, which display wild-type-like morphology and resistance. M2 progeny were screened for mutant, snc1-enhancing (muse) mutants displaying a reversion to snc1-like phenotypes. The muse9 mos4 snc1 triple mutant was found to exhibit dwarf morphology, elevated expression of the pPR2-GUS defense marker reporter gene and enhanced resistance to the oomycete pathogen Hyaloperonospora arabidopsidis Noco2. Via map-based cloning and Illumina sequencing, it was determined that the muse9 mutation is in the gene encoding the SWI/SNF chromatin remodeler SYD (SPLAYED), and was thus renamed syd-10. The syd-10 single mutant has no observable alteration from wild-type-like resistance, although the syd-4 T-DNA insertion allele displays enhanced resistance to the bacterial pathogen Pseudomonas syringae pv. maculicola ES4326. Transcription of SNC1 is increased in both syd-4 and syd-10. These data suggest that SYD plays a subtle, specific role in the regulation of SNC1 expression and SNC1-mediated immunity. SYD may work with other proteins at the chromatin level to repress SNC1 transcription; such regulation is important for fine-tuning the expression of NLR-encoding genes to prevent unpropitious autoimmunity.
Keywords: Cell Biology; Plant Science; Physiology; General Medicine

Observation of laser-induced electronic structure in oriented polyatomic molecules - Kraus, P. M.; Tolstikhin, O. I.; Baykusheva, Denitsa Rangelova; Rupenyan, A.; Schneider, J.; Bisgaard, C. Z.; Morishita, T.; Jensen, F.; Madsen, L. B.; Wörner, H. J. (Nature Communications)
All attosecond time-resolved measurements have so far relied on the use of intense near-infrared laser pulses. In particular, attosecond streaking, laser-induced electron diffraction and high-harmonic generation all make use of non-perturbative light–matter interactions. Remarkably, the effect of the strong laser field on the studied sample has often been neglected in previous studies. Here we use high-harmonic spectroscopy to measure laser-induced modifications of the electronic structure of molecules. We study high-harmonic spectra of spatially oriented CH3F and CH3Br as generic examples of polar polyatomic molecules. We accurately measure intensity ratios of even and odd-harmonic orders, and of the emission from aligned and unaligned molecules. We show that these robust observables reveal a substantial modification of the molecular electronic structure by the external laser field. Our insights offer new challenges and opportunities for a range of emerging strong-field attosecond spectroscopies.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Cancer/Testis antigen PASD1 silences the circadian clock - Michael, Alicia Kathleen; Harvey, Stacy L.; Sammons, Patrick J.; Anderson, Amanda P.; Kopalle, Hema M.; Banham, Alison H.; Partch, Carrie L. (Molecular Cell)
The circadian clock orchestrates global changes in transcriptional regulation on a daily basis via the bHLH-PAS transcription factor CLOCK:BMAL1. Pathways driven by other bHLH-PAS transcription factors have a homologous repressor that modulates activity on a tissue-specific basis, but none have been identified for CLOCK:BMAL1. We show here that the cancer/testis antigen PASD1 fulfills this role to suppress circadian rhythms. PASD1 is evolutionarily related to CLOCK and interacts with the CLOCK:BMAL1 complex to repress transcriptional activation. Expression of PASD1 is restricted to germline tissues in healthy individuals but can be induced in cells of somatic origin upon oncogenic transformation. Reducing PASD1 in human cancer cells significantly increases the amplitude of transcriptional oscillations to generate more robust circadian rhythms. Our results describe a function for a germline-specific protein in regulation of the circadian clock and provide a molecular link from oncogenic transformation to suppression of circadian rhythms.
Keywords: Cell Biology; Molecular Biology

Cytosolic BMAL1 moonlights as a translation factor - Michael, Alicia Kathleen; Asimgil, Hande; Partch, Carrie L. (Trends in Biochemical Sciences)
It is widely recognized that BMAL1 is an essential subunit of the primary transcription factor that drives rhythmic circadian transcription in the nucleus. In a surprising turn, Lipton et al. now show that BMAL1 rhythmically interacts with translational machinery in the cytosol to stimulate protein synthesis in response to mTOR signaling.
Keywords: Molecular Biology; Biochemistry

Molecular and cellular mechanisms of development underlying congenital diseases - Hashimoto, Masakazu; Morita, Hitoshi; Ueno, Naoto (Congenital Anomalies)
In the last several decades, developmental biology has clarified the molecular mechanisms of embryogenesis and organogenesis. In particular, it has demonstrated that the “tool-kit genes” essential for regulating developmental processes are not only highly conserved among species, but are also used as systems at various times and places in an organism to control distinct developmental events. Therefore, mutations in many of these tool-kit genes may cause congenital diseases involving morphological abnormalities. This link between genes and abnormal morphological phenotypes underscores the importance of understanding how cells behave and contribute to morphogenesis as a result of gene function. Recent improvements in live imaging and in quantitative analyses of cellular dynamics will advance our understanding of the cellular pathogenesis of congenital diseases associated with aberrant morphologies. In these studies, it is critical to select an appropriate model organism for the particular phenomenon of interest.
Keywords: Developmental Biology; Embryology; General Medicine; Pediatrics; Perinatology; and Child Health

Nuclear pores set the speed limit for mitosis - Buchwalter, Abigail; HETZER, Martin W (Cell)
The spindle assembly checkpoint prevents separation of sister chromatids until each kinetochore is attached to the mitotic spindle. Rodriguez-Bravo et al. report that the nuclear pore complex scaffolds spindle assembly checkpoint signaling in interphase, providing a store of inhibitory signals that limits the speed of the subsequent mitosis.
Keywords: General Biochemistry; Genetics and Molecular Biology

Nup50 is required for cell differentiation and exhibits transcription-dependent dynamics - Buchwalter, Abigail L.; Liang, Yun; HETZER, Martin W (Molecular Biology of the Cell)
The nuclear pore complex (NPC) plays a critical role in gene expression by mediating import of transcription regulators into the nucleus and export of RNA transcripts to the cytoplasm. Emerging evidence suggests that in addition to mediating transport, a subset of nucleoporins (Nups) engage in transcriptional activation and elongation at genomic loci that are not associated with NPCs. The underlying mechanism and regulation of Nup mobility on and off nuclear pores remain unclear. Here we show that Nup50 is a mobile Nup with a pronounced presence both at the NPC and in the nucleoplasm that can move between these different localizations. Strikingly, the dynamic behavior of Nup50 in both locations is dependent on active transcription by RNA polymerase II and requires the N-terminal half of the protein, which contains importin α– and Nup153-binding domains. However, Nup50 dynamics are independent of importin α, Nup153, and Nup98, even though the latter two proteins also exhibit transcription-dependent mobility. Of interest, depletion of Nup50 from C2C12 myoblasts does not affect cell proliferation but inhibits differentiation into myotubes. Taken together, our results suggest a transport-independent role for Nup50 in chromatin biology that occurs away from the NPC.
Keywords: Cell Biology; Molecular Biology

Breaching the nuclear envelope in development and disease - Hatch, Emily; HETZER, Martin W (Journal of Cell Biology)
In eukaryotic cells the nuclear genome is enclosed by the nuclear envelope (NE). In metazoans, the NE breaks down in mitosis and it has been assumed that the physical barrier separating nucleoplasm and cytoplasm remains intact during the rest of the cell cycle and cell differentiation. However, recent studies suggest that nonmitotic NE remodeling plays a critical role in development, virus infection, laminopathies, and cancer. Although the mechanisms underlying these NE restructuring events are currently being defined, one common theme is activation of protein kinase C family members in the interphase nucleus to disrupt the nuclear lamina, demonstrating the importance of the lamina in maintaining nuclear integrity.
Keywords: Cell Biology

Relax: The analysis of biomolecular kinetics and thermodynamics using NMR relaxation dispersion data - Morin, Sébastien; Linnet, Troels E; Lescanne, Mathilde; Schanda, Paul; Thompson, Gary S; Tollinger, Martin; Teilum, Kaare; Gagné, Stéphane; Marion, Dominique; Griesinger, Christian; Blackledge, Martin; d’Auvergne, Edward J (Bioinformatics)
Nuclear magnetic resonance (NMR) is a powerful tool for observing the motion of biomolecules at the atomic level. One technique, the analysis of relaxation dispersion phenomenon, is highly suited for studying the kinetics and thermodynamics of biological processes. Built on top of the relax computational environment for NMR dynamics is a new dispersion analysis designed to be comprehensive, accurate and easy-to-use. The software supports more models, both numeric and analytic, than current solutions. An automated protocol, available for scripting and driving the graphical user interface (GUI), is designed to simplify the analysis of dispersion data for NMR spectroscopists. Decreases in optimization time are granted by parallelization for running on computer clusters and by skipping an initial grid search by using parameters from one solution as the starting point for another —using analytic model results for the numeric models, taking advantage of model nesting, and using averaged non-clustered results for the clustered analysis.
Keywords: Statistics and Probability; Computational Theory and Mathematics; Biochemistry; Molecular Biology; Computational Mathematics; Computer Science Applications

Nanoporous frameworks exhibiting multiple stimuli responsiveness - Kundu, Pintu K.; Olsen, Gregory L.; Kiss, Vladimir; Klajn, Rafal (Nature Communications)
Nanoporous frameworks are polymeric materials built from rigid molecules, which give rise to their nanoporous structures with applications in gas sorption and storage, catalysis and others. Conceptually new applications could emerge, should these beneficial properties be manipulated by external stimuli in a reversible manner. One approach to render nanoporous frameworks responsive to external signals would be to immobilize molecular switches within their nanopores. Although the majority of molecular switches require conformational freedom to isomerize, and switching in the solid state is prohibited, the nanopores may provide enough room for the switches to efficiently isomerize. Here we describe two families of nanoporous materials incorporating the spiropyran molecular switch. These materials exhibit a variety of interesting properties, including reversible photochromism and acidochromism under solvent-free conditions, light-controlled capture and release of metal ions, as well reversible chromism induced by solvation/desolvation.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Dynamic association of NUP98 with the human genome - Liang, Yun; Franks, Tobias M.; Marchetto, Maria C.; Gage, Fred H.; HETZER, Martin W (PLoS Genetics)
Faithful execution of developmental gene expression programs occurs at multiple levels and involves many different components such as transcription factors, histone-modification enzymes, and mRNA processing proteins. Recent evidence suggests that nucleoporins, well known components that control nucleo-cytoplasmic trafficking, have wide-ranging functions in developmental gene regulation that potentially extend beyond their role in nuclear transport. Whether the unexpected role of nuclear pore proteins in transcription regulation, which initially has been described in fungi and flies, also applies to human cells is unknown. Here we show at a genome-wide level that the nuclear pore protein NUP98 associates with developmentally regulated genes active during human embryonic stem cell differentiation. Overexpression of a dominant negative fragment of NUP98 levels decreases expression levels of NUP98-bound genes. In addition, we identify two modes of developmental gene regulation by NUP98 that are differentiated by the spatial localization of NUP98 target genes. Genes in the initial stage of developmental induction can associate with NUP98 that is embedded in the nuclear pores at the nuclear periphery. Alternatively, genes that are highly induced can interact with NUP98 in the nuclear interior, away from the nuclear pores. This work demonstrates for the first time that NUP98 dynamically associates with the human genome during differentiation, revealing a role of a nuclear pore protein in regulating developmental gene expression programs.
Keywords: Cancer Research; Genetics (clinical); Genetics; Molecular Biology; Ecology; Evolution; Behavior and Systematics

Identification of long-lived proteins reveals exceptional stability of essential cellular structures - Toyama, Brandon H.; Savas, Jeffrey N.; Park, Sung Kyu; Harris, Michael S.; Ingolia, Nicholas T.; Yates, John R.; HETZER, Martin W (Cell)
Intracellular proteins with long lifespans have recently been linked to age-dependent defects, ranging from decreased fertility to the functional decline of neurons. Why long-lived proteins exist in metabolically active cellular environments and how they are maintained over time remains poorly understood. Here, we provide a system-wide identification of proteins with exceptional lifespans in the rat brain. These proteins are inefficiently replenished despite being translated robustly throughout adulthood. Using nucleoporins as a paradigm for long-term protein persistence, we found that nuclear pore complexes (NPCs) are maintained over a cell’s life through slow but finite exchange of even its most stable subcomplexes. This maintenance is limited, however, as some nucleoporin levels decrease during aging, providing a rationale for the previously observed age-dependent deterioration of NPC function. Our identification of a long-lived proteome reveals cellular components that are at increased risk for damage accumulation, linking long-term protein persistence to the cellular aging process.
Keywords: General Biochemistry; Genetics and Molecular Biology

Catastrophic nuclear envelope collapse in cancer cell micronuclei - Hatch, Emily M.; Fischer, Andrew H.; Deerinck, Thomas J.; HETZER, Martin W (Cell)
During mitotic exit, missegregated chromosomes can recruit their own nuclear envelope (NE) to form micronuclei (MN). MN have reduced functioning compared to primary nuclei in the same cell, although the two compartments appear to be structurally comparable. Here we show that over 60% of MN undergo an irreversible loss of compartmentalization during interphase due to NE collapse. This disruption of the MN, which is induced by defects in nuclear lamina assembly, drastically reduces nuclear functions and can trigger massive DNA damage. MN disruption is associated with chromatin compaction and invasion of endoplasmic reticulum (ER) tubules into the chromatin. We identified disrupted MN in both major subtypes of human non-small-cell lung cancer, suggesting that disrupted MN could be a useful objective biomarker for genomic instability in solid tumors. Our study shows that NE collapse is a key event underlying MN dysfunction and establishes a link between aberrant NE organization and aneuploidy.
Keywords: General Biochemistry; Genetics and Molecular Biology

The role of Nup98 in transcription regulation in healthy and diseased cells - Franks, Tobias M.; HETZER, Martin W (Trends in Cell Biology)
Nuclear pore complex (NPC) proteins are known for their critical roles in regulating nucleocytoplasmic traffic of macromolecules across the nuclear envelope. However, recent findings suggest that some nucleoporins (Nups), including Nup98, have additional functions in developmental gene regulation. Nup98, which exhibits transcription-dependent mobility at the NPC but can also bind chromatin away from the nuclear envelope, is frequently involved in chromosomal translocations in a subset of patients suffering from acute myeloid leukemia (AML). A common paradigm suggests that Nup98 translocations cause aberrant transcription when they are recuited to aberrant genomic loci. Importantly, this model fails to account for the potential loss of wild type (WT) Nup98 function in the presence of Nup98 translocation mutants. Here we examine how the cell might regulate Nup98 nucleoplasmic protein levels to control transcription in healthy cells. In addition, we discuss the possibility that dominant negative Nup98 fusion proteins disrupt the transcriptional activity of WT Nup98 in the nucleoplasm to drive AML.
Keywords: Cell Biology

Protein homeostasis: Live long, won't prosper - Toyama, Brandon H.; HETZER, Martin W (Nature Reviews Molecular Cell Biology)
Protein turnover is an effective way of maintaining a functional proteome, as old and potentially damaged polypeptides are destroyed and replaced by newly synthesized copies. An increasing number of intracellular proteins, however, have been identified that evade this turnover process and instead are maintained over a cell's lifetime. This diverse group of long-lived proteins might be particularly prone to accumulation of damage and thus have a crucial role in the functional deterioration of key regulatory processes during ageing.
Keywords: Cell Biology; Molecular Biology

Oligomeric states along the folding pathways of β2-microglobulin: Kinetics, thermodynamics, and structure - Rennella, E.; Cutuil, T.; Schanda, Paul; Ayala, I.; Gabel, F.; Forge, V.; Corazza, A.; Esposito, G.; Brutscher, B. (Journal of Molecular Biology)
The transition of proteins from their soluble functional state to amyloid fibrils and aggregates is associated with the onset of several human diseases. Protein aggregation often requires some structural reshaping and the subsequent formation of intermolecular contacts. Therefore, the study of the conformation of excited protein states and their ability to form oligomers is of primary importance for understanding the molecular basis of amyloid fibril formation. Here, we investigated the oligomerization processes that occur along the folding of the amyloidogenic human protein β2-microglobulin. The combination of real-time two-dimensional NMR data with real-time small-angle X-ray scattering measurements allowed us to derive thermodynamic and kinetic information on protein oligomerization of different conformational states populated along the folding pathways. In particular, we could demonstrate that a long-lived folding intermediate (I-state) has a higher propensity to oligomerize compared to the native state. Our data agree well with a simple five-state kinetic model that involves only monomeric and dimeric species. The dimers have an elongated shape with the dimerization interface located at the apical side of β2-microglobulin close to Pro32, the residue that has a trans conformation in the I-state and a cis conformation in the native (N) state. Our experimental data suggest that partial unfolding in the apical half of the protein close to Pro32 leads to an excited state conformation with enhanced propensity for oligomerization. This excited state becomes more populated in the transient I-state due to the destabilization of the native conformation by the trans-Pro32 configuration.
Keywords: Molecular Biology

Large-scale cytological profiling for functional analysis of bioactive compounds - Woehrmann, Marcos H.; Bray, Walter M.; Durbin, James K.; Nisam, Sean C.; Michael, Alicia Kathleen; Glassey, Emerson; Stuart, Joshua M.; Lokey, R. Scott (Molecular BioSystems)
Cytological profiling (CP) is an unbiased image-based screening technique that uses automated microscopy and image analysis to profile compounds based on numerous quantifiable phenotypic features. We used CP to evaluate a library of nearly 500 compounds with documented mechanisms of action (MOAs) spanning a wide range of biological pathways. We developed informatics techniques for generating dosage-independent phenotypic “fingerprints” for each compound, and for quantifying the likelihood that a compound's CP fingerprint corresponds to its annotated MOA. We identified groups of features that distinguish classes with closely related phenotypes, such as microtubule poisons vs. HSP90 inhibitors, and DNA synthesis vs. proteasome inhibitors. We tested several cases in which cytological profiles indicated novel mechanisms, including a tyrphostin kinase inhibitor involved in mitochondrial uncoupling, novel microtubule poisons, and a nominal PPAR-gamma ligand that acts as a proteasome inhibitor, using independent biochemical assays to confirm the MOAs predicted by the CP signatures. We also applied maximal-information statistics to identify correlations between cytological features and kinase inhibitory activities by combining the CP fingerprints of 24 kinase inhibitors with published data on their specificities against a diverse panel of kinases. The resulting analysis suggests a strategy for probing the biological functions of specific kinases by compiling cytological data from inhibitors of varying specificities.
Keywords: Molecular Biology; Biotechnology

Outfits for different occasions: tissue-specific roles of Nuclear Envelope proteins - Gomez-Cavazos, J Sebastian; HETZER, Martin W (Current Opinion in Cell Biology)
The Nuclear Envelope (NE) contains over 100 different proteins that associate with nuclear components such as chromatin, the lamina and the transcription machinery. Mutations in genes encoding NE proteins have been shown to result in tissue-specific defects and disease, suggesting cell-type specific differences in NE composition and function. Consistent with these observations, recent studies have revealed unexpected functions for numerous NE associated proteins during cell differentiation and development. Here we review the latest insights into the roles played by the NE in cell differentiation, development, disease and aging, focusing primarily on inner nuclear membrane (INM) proteins and nuclear pore components.
Keywords: Cell Biology

Transient nuclear envelope rupturing during interphase in human cancer cells - Vargas, Jesse D.; Hatch, Emily M.; Anderson, Daniel J.; HETZER, Martin W (Nucleus)
Neoplastic cells are often characterized by specific morphological abnormalities of the nuclear envelope (NE), which have been used for cancer diagnosis for more than a century. The NE is a double phospholipid bilayer that encapsulates the nuclear genome, regulates all nuclear trafficking of RNAs and proteins and prevents the passive diffusion of macromolecules between the nucleoplasm and the cytoplasm. Whether there is a consequence to the proper functioning of the cell and loss of structural integrity of the nucleus remains unclear. Using live cell imaging, we characterize a phenomenon wherein nuclei of several proliferating human cancer cell lines become temporarily ruptured during interphase. Strikingly, NE rupturing was associated with the mislocalization of nucleoplasmic and cytoplasmic proteins and, in the most extreme cases, the entrapment of cytoplasmic organelles in the nuclear interior. In addition, we observed the formation of micronuclei-like structures during interphase and the movement of chromatin out of the nuclear space. The frequency of these NE rupturing events was higher in cells in which the nuclear lamina, a network of intermediate filaments providing mechanical support to the NE, was not properly formed. Our data uncover the existence of a NE instability that has the potential to change the genomic landscape of cancer cells.
Keywords: Cell Biology

A change in nuclear pore complex composition regulates cell differentiation - D'Angelo, Maximiliano A.; Gomez-Cavazos, J. Sebastian; Mei, Arianna; Lackner, Daniel H.; HETZER, Martin W (Developmental Cell)
Nuclear pore complexes (NPCs) are built from ∼30 different proteins called nucleoporins or Nups. Previous studies have shown that several Nups exhibit cell-type-specific expression and that mutations in NPC components result in tissue-specific diseases. Here we show that a specific change in NPC composition is required for both myogenic and neuronal differentiation. The transmembrane nucleoporin Nup210 is absent in proliferating myoblasts and embryonic stem cells (ESCs) but becomes expressed and incorporated into NPCs during cell differentiation. Preventing Nup210 production by RNAi blocks myogenesis and the differentiation of ESCs into neuroprogenitors. We found that the addition of Nup210 to NPCs does not affect nuclear transport but is required for the induction of genes that are essential for cell differentiation. Our results identify a single change in NPC composition as an essential step in cell differentiation and establish a role for Nup210 in gene expression regulation and cell fate determination.
Keywords: Developmental Biology; Cell Biology; General Biochemistry; Genetics and Molecular Biology; Molecular Biology

RNP export by nuclear envelope budding - Hatch, Emily M.; HETZER, Martin W (Cell)
Nuclear export of mRNAs is thought to occur exclusively through nuclear pore complexes. In this issue of Cell, Speese et al. identify an alternate pathway for mRNA export in muscle cells where ribonucleoprotein complexes involved in forming neuromuscular junctions transit the nuclear envelope by fusing with and budding through the nuclear membrane.
Keywords: General Biochemistry; Genetics and Molecular Biology

POM121 and Sun1 play a role in early steps of interphase NPC assembly - Talamas, Jessica A.; HETZER, Martin W (Journal of Cell Biology)
Nuclear pore complexes (NPCs) assemble at the end of mitosis during nuclear envelope (NE) reformation and into an intact NE as cells progress through interphase. Although recent studies have shown that NPC formation occurs by two different molecular mechanisms at two distinct cell cycle stages, little is known about the molecular players that mediate the fusion of the outer and inner nuclear membranes to form pores. In this paper, we provide evidence that the transmembrane nucleoporin (Nup), POM121, but not the Nup107–160 complex, is present at new pore assembly sites at a time that coincides with inner nuclear membrane (INM) and outer nuclear membrane (ONM) fusion. Overexpression of POM121 resulted in juxtaposition of the INM and ONM. Additionally, Sun1, an INM protein that is known to interact with the cytoskeleton, was specifically required for interphase assembly and localized with POM121 at forming pores. We propose a model in which POM121 and Sun1 interact transiently to promote early steps of interphase NPC assembly.
Keywords: Cell Biology

Functional interactions between nucleoporins and chromatin - Liang, Yun; HETZER, Martin W (Current Opinion in Cell Biology)
As the gatekeepers of the eukaryotic cell nucleus, nuclear pore complexes (NPCs) mediate all molecular trafficking between the nucleoplasm and the cytoplasm. In recent years, transport-independent functions of NPC components, nucleoporins, have been identified including roles in chromatin organization and gene regulation. Here, we summarize our current view of the NPC as a dynamic hub for the integration of chromatin regulation and nuclear trafficking and discuss the functional interplay between nucleoporins and the nuclear genome.
Keywords: Cell Biology

Editorial overview - HETZER, Martin W; Cavalli, Giacomo (Current Opinion in Cell Biology)
Keywords: Cell Biology

Nuclear pore complexes: Guardians of the nuclear genome - Capelson, M.; Doucet, C.; HETZER, Martin W (Cold Spring Harbor Symposia on Quantitative Biology)
Eukaryotic cell function depends on the physical separation of nucleoplasmic and cytoplasmic components by the nuclear envelope (NE). Molecular communication between the two compartments involves active, signal-mediated trafficking, a function that is exclusively performed by nuclear pore complexes (NPCs). The individual NPC components and the mechanisms that are involved in nuclear trafficking are well documented and have become textbook knowledge. However, in addition to their roles as nuclear gatekeepers, NPC components-nucleoporins-have been shown to have critical roles in chromatin organization and gene regulation. These findings have sparked new enthusiasm to study the roles of this multiprotein complex in nuclear organization and explore novel functions that in some cases appear to go beyond a role in transport. Here, we discuss our present view of NPC biogenesis, which is tightly linked to proper cell cycle progression and cell differentiation. In addition, we summarize new data suggesting that NPCs represent dynamic hubs for the integration of gene regulation and nuclear transport processes.
Keywords: Genetics; Molecular Biology; Biochemistry

The nuclear envelope - HETZER, Martin W (Cold Spring Harbor Perspectives in Biology)
The nuclear envelope (NE) is a highly regulated membrane barrier that separates the nucleus from the cytoplasm in eukaryotic cells. It contains a large number of different proteins that have been implicated in chromatin organization and gene regulation. Although the nuclear membrane enables complex levels of gene expression, it also poses a challenge when it comes to cell division. To allow access of the mitotic spindle to chromatin, the nucleus of metazoans must completely disassemble during mitosis, generating the need to re-establish the nuclear compartment at the end of each cell division. Here, I summarize our current understanding of the dynamic remodeling of the NE during the cell cycle.
Keywords: General Biochemistry; Genetics and Molecular Biology

Chromatin-bound nuclear pore components regulate gene expression in higher eukaryotes - Capelson, Maya; Liang, Yun; Schulte, Roberta; Mair, William; Wagner, Ulrich; HETZER, Martin W (Cell)
Nuclear pore complexes have recently been shown to play roles in gene activation; however their potential involvement in metazoan transcription remains unclear. Here we show that the nucleoporins Sec13, Nup98, and Nup88, as well as a group of FG-repeat nucleoporins, bind to the Drosophila genome at functionally distinct loci that often do not represent nuclear envelope contact sites. Whereas Nup88 localizes to silent loci, Sec13, Nup98, and a subset of FG-repeat nucleoporins bind to developmentally regulated genes undergoing transcription induction. Strikingly, RNAi-mediated knockdown of intranuclear Sec13 and Nup98 specifically inhibits transcription of their target genes and prevents efficient reactivation of transcription after heat shock, suggesting an essential role of NPC components in regulating complex gene expression programs of multicellular organisms.
Keywords: General Biochemistry; Genetics and Molecular Biology

Cell cycle-dependent differences in nuclear pore complex assembly in metazoa - Doucet, Christine M.; Talamas, Jessica A.; HETZER, Martin W (Cell)
In metazoa, nuclear pore complexes (NPCs) assemble from disassembled precursors into a reforming nuclear envelope (NE) at the end of mitosis and into growing intact NEs during interphase. Here, we show via RNAi-mediated knockdown that ELYS, a nucleoporin critical for the recruitment of the essential Nup107/160 complex to chromatin, is required for NPC assembly at the end of mitosis but not during interphase. Conversely, the transmembrane nucleoporin POM121 is critical for the incorporation of the Nup107/160 complex into new assembly sites specifically during interphase. Strikingly, recruitment of the Nup107/160 complex to an intact NE involves a membrane curvature-sensing domain of its constituent Nup133, which is not required for postmitotic NPC formation. Our results suggest that in organisms with open mitosis, NPCs assemble via two distinct mechanisms to accommodate cell cycle-dependent differences in NE topology.
Keywords: General Biochemistry; Genetics and Molecular Biology